Film roll and its manufacturing method

JP7652080B2Active Publication Date: 2025-03-27KONICA MINOLTA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021562524
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-11-09
Publication Date
2025-03-27
Estimated Expiration
2040-11-09

AI Technical Summary

Benefits of technology

【0022】 本発明の上記手段により、優れたアンチブロッキング性を有し、粒子とフィルム面との接触による傷の発生や粒子の脱落を抑制したフィルムロール及びその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652080000010
    Figure 0007652080000010
  • Figure 0007652080000011
    Figure 0007652080000011
  • Figure 0007652080000012
    Figure 0007652080000012
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a film roll that has excellent anti-blocking properties and that suppresses particle shedding as well as defects caused by contact between particles and a film surface; and a production method for the film roll. This film roll is formed by providing a functional layer on one surface of a base material film and is characterized in that the base material film contains particles A and has a modulus of elasticity of 1.0–3.0 GPa at 25°C and 55% RH and in that the functional layer contains particles B and a binder resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film roll and a manufacturing method thereof, and more particularly to a film roll having excellent antiblocking properties and suppressing the occurrence of scratches and the falling off of particles due to contact between particles and the film surface. [Background technology]

[0002] In recent years, the applications of liquid crystal displays have expanded. Therefore, higher durability is required for the members used. For this reason, it is desired that the physical properties and optical properties of the polarizing plate protective film do not change due to changes in the environment, and, other than the conventionally used cellulose-based resin film, for example, a cyclic olefin-based resin film, an acrylic-based resin film, or a polyester-based resin film has begun to be used.

[0003] Cyclic olefin resin films are generally formed into a film shape by a melt film forming method and stored as rolled films. Furthermore, to prevent blocking, which is a problem caused by films sticking to each other in a rolled form, the cyclic olefin resin film may be used as a substrate and a functional layer having an anti-blocking function may be provided on one side of the substrate, ultimately producing a laminated film. It has been disclosed that such a functional layer is formed by applying a composition containing fine particles in a binder resin to one side of the substrate (see, for example, Patent Document 1).

[0004] On the other hand, in addition to the above-mentioned melt casting method (also called melt casting method), a representative method for producing resin films is the solution casting method (also called solution casting method). The solution casting method is characterized by a lower temperature during the processing step compared to the melt casting method, and therefore it is said that there is a lot of room for improving functionality by using various additives. For this reason, it is advantageous as a manufacturing method for responding to the diverse performance requirements that accompany the expansion of applications for liquid crystal displays.

[0005] Therefore, the present inventors prepared an acrylic resin film using a solution casting method, and used it as a substrate film to form a laminated film by coating one side with a resin composition containing fine particles, but contrary to expectations, the anti-blocking property was insufficient. Furthermore, when a laminated film was similarly prepared using a cyclic olefin resin, the anti-blocking property was also insufficient.

[0006] Furthermore, as described in Patent Document 1, when a laminated film is produced by preparing a cyclic olefin resin film by a melt casting method and applying a resin composition containing fine particles, it has been found that problems such as scratches caused by the fine particles due to contact between films and the falling off of the fine particles in the layer formed by coating occur. Furthermore, the scratches caused by contact between these films and the falling off of the fine particles in the layer formed by coating were also confirmed even when a base film produced by a solution casting method was used.

[0007] In examining these phenomena, it was inferred that films containing materials with excellent water resistance, such as cyclic olefin resins and acrylic resins, have a relatively low elastic modulus compared to cellulose resin films, and that due to this reduced elastic modulus, even if a resin composition containing fine particles is applied to one side, the anti-blocking properties are insufficient, and problems such as scratches caused by fine particles due to contact between films and the falling off of fine particles in a layer applied by coating are likely to occur.

[0008] On the other hand, the technology of laminating a coating solution containing fine particles on the surface of a component is being studied, although not in the field of optical films and for purposes other than imparting anti-blocking properties. (See, for example, Patent Document 2.)

[0009] Patent Document 2 considers applying a coating solution containing fine particles twice with a drying process in between, but even when the coating method described in Patent Document 2 is used on the above-mentioned laminated film, it is difficult to solve problems such as scratches and the falling off of fine particles. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Patent No. 5594096 [Patent Document 2] JP 2008-007893 A Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above problems and circumstances, and an object of the present invention is to provide a film roll having excellent anti-blocking properties and capable of suppressing the generation of scratches and the falling off of particles due to contact between particles and the film surface, and a method for manufacturing the same. [Means for solving the problem]

[0012] In the course of investigating the causes of the above problems in order to solve the above problems, the present inventors have found that a film configuration in which a functional layer containing particles B is provided on a base film having an elastic modulus within a specific range and containing particles A can provide a film roll and a manufacturing method thereof that have excellent anti-blocking properties and suppress the occurrence of scratches and particle drop-off due to contact between the particles and the film surface.

[0013] That is, the above-mentioned problems of the present invention are solved by the following means.

[0014] 1. A film roll having a functional layer on one side of a base film, The elastic modulus of the base film at 25°C and 55% RH is within the range of 1.0 to 3.0 GPa; The base film contains particles A, and The functional layer contains a binder resin and particles B. death , The number average particle diameter of the primary particles of the particles A is within a range of 5 to 20 nm, the number average particle diameter of the primary particles of the particles B is within a range of 50 to 500 nm, and the ratio R (RB / RA) of the number average particle diameter (RB) of the primary particles of the particles B to the number average particle diameter (RA) of the primary particles of the particles A is within a range of 2.5 to 100. A film roll comprising:

[0015] 2. The film roll described in item 1, wherein the base film is a long film formed by casting a solution containing a resin and the particles A.

[0016] 3. The film roll described in item 1 or 2, wherein the base film contains an acrylic resin or a cyclic olefin resin.

[0017] 4. The film roll described in any one of items 1 to 3, wherein the binder resin contained in the functional layer is a polyolefin resin.

[0019] 5 The particle A and the particle B are silica particles. 4 Item 1. The film roll according to any one of items 1 to 9.

[0020] 6 The functional layer is composed of a plurality of layers, and the surface layer does not contain the particles B. 5 Item 1. The film roll according to any one of items 1 to 9.

[0021] 7 .Items 1 to 5 6 A method for producing the film roll according to any one of claims 1 to 5, comprising the steps of: A method for producing a film roll, comprising forming the base film by a solution casting method, and forming the functional layer by a wet coating method. 8 In forming the coating film of the functional layer by the wet coating method, coating is performed two or more times, In the first coating, a coating liquid containing the binder resin and the particles B is applied onto the substrate film to form a coating film, The second and subsequent coatings are applied by forming a coating film on the coating film formed by the first coating, The second or subsequent coating, which is the last coating of the surface layer, forms a coating film using a coating liquid that contains the binder resin but does not contain the particles B. The first feature is 7 Item 1. A method for producing a film roll according to item 1. Effect of the Invention

[0022] According to the above-mentioned means of the present invention, it is possible to provide a film roll having excellent antiblocking properties and suppressing the occurrence of scratches due to contact between particles and the film surface and the dropping off of particles, and a manufacturing method thereof.

[0023] Although the mechanism by which the effects of the present invention are expressed or the mechanism of action has not been clarified, it is speculated as follows.

[0024] The film roll of the present invention is a laminated film roll having a functional layer provided on one side of a base film, the base film having a relatively low elastic modulus of 1.0 to 3.0 GPa, the base film containing particles A, and the functional layer containing a binder resin and particles B.

[0025] The improvement of anti-blocking properties, which is the objective of the present invention, is presumably achieved by preventing the desired uneven surface from being formed by adding particle A to the base film in advance, which prevents particle B, which is contained in the functional layer and would normally form an uneven surface, from sinking into tiny gaps generated by solution casting of the base film, thereby forming an appropriately uneven surface in the functional layer.

[0026] Furthermore, the occurrence of film scratches and particle drop-off caused by particles in the functional layer can be suppressed by adding particle A to the base film in advance to form unevenness on the surface, and by providing a functional layer containing particle B, the particle B is pushed up by the unevenness of particle A, making it possible to sufficiently form large unevenness that contributes to anti-blocking properties on the functional layer surface, thereby ensuring the desired anti-blocking properties. Furthermore, by covering the particle B that forms the unevenness with a binder resin, the number of particles exposed from the functional layer surface without being covered is reduced, and the occurrence of film scratches and particle drop-off caused by the particles can be further suppressed. [Brief description of the drawings]

[0027] [Figure 1A] FIG. 1 is a schematic diagram illustrating the function of particles contained in a base film and a functional layer of a film roll having a base film and a functional layer formed by melt casting. [Figure 1B] An enlarged view of the film on the core of a film roll [Figure 1C] Schematic diagram of a film roll having a base film and a functional layer formed by solution casting as a comparative example. [Figure 1D] An enlarged view of the film on the core of a film roll [Figure 1E] FIG. 1 is a schematic diagram of a film roll of the present invention, which has a substrate film containing particles formed by solution casting and a functional layer. [Figure 1F] An enlarged view of the film on the core of a film roll [Figure 2A] Cross-sectional view of the film roll of the present invention [Figure 2B] 1 is a cross-sectional view of a film roll showing a more preferred embodiment of the present invention; [Diagram 3] FIG. 1 is a schematic diagram illustrating a preferred embodiment in which a functional layer is formed on a substrate film. [Figure 4] Schematic diagram showing the method of producing a film by solution casting [Diagram 5] Schematic diagram of film production line [Figure 6] Plan view of the winding device DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] The film roll of the present invention is a film roll having a functional layer provided on one surface of a base film, characterized in that the elastic modulus of the base film at 25°C and 55% RH is within a range of 1.0 to 3.0 GPa, the base film contains particles A, and the functional layer contains a binder resin and particles B. This feature is a technical feature common to or corresponding to the following embodiments.

[0029] As an embodiment of the present invention, from the viewpoint of expressing the effects of the present invention, it is preferable that the base film is a long film formed by casting a solution containing a resin and the particles A, because the temperature during the processing step is low and therefore various additives can be used to enhance functionality.

[0030] It is preferable that the substrate film contains an acrylic resin or a cyclic olefin resin from the viewpoint of obtaining a high-quality optical film in which physical properties such as water resistance and optical properties are unlikely to change even in high-temperature and high-humidity environments.

[0031] The binder resin contained in the functional layer is preferably a polyolefin-based resin, which is a water-based resin, from the viewpoint of coatability by wet coating.

[0032] From the viewpoint of balancing antiblocking properties and transparency, it is preferable that the number average particle size of the primary particles of the particles A is within a range of 5 to 20 nm, the number average particle size of the primary particles of the particles B is within a range of 50 to 500 nm, and the ratio R (RB / RA) of the number average particle size (RB) of the primary particles of the particles B to the number average particle size (RA) of the primary particles of the particles A is within a range of 2.5 to 100.

[0033] Moreover, it is preferable that the particles A and the particles B are silica particles from the viewpoints of ease of handling and transparency as an optical film.

[0034] Furthermore, it is preferable that the functional layer is composed of a plurality of layers, and that the surface layer does not contain the particles B, from the viewpoint of preventing scratches on the film surface and particle dropout.

[0035] The method for producing the film roll of the present invention is characterized in that the base film is formed by a solution casting method, and the functional layer is formed by a wet coating method.

[0036] Furthermore, in the method for producing a film roll, it is preferable that in forming a coating film of a functional layer by the wet coating method, coating is performed two or more times, the first coating is performed by forming a coating film on the base film using a coating liquid containing the binder resin and the particles B, and the second and subsequent coatings are performed by forming further coating films on the coating film formed by the first coating, and the second and subsequent coatings are performed last to coat the surface layer by forming a coating film using a coating liquid containing the binder resin but not the particles B.

[0037] The present invention, its components, and embodiments for carrying out the present invention will be described in detail below. In this application, the symbol "to" is used to mean that the numerical values ​​before and after the symbol "to" are included as the lower limit and upper limit.

[0038] <<Outline of the film roll of the present invention>> The film roll of the present invention is a film roll having a functional layer provided on one side of a base film, characterized in that the elastic modulus of the base film at 25°C and 55% RH is in the range of 1.0 to 3.0 GPa, the base film contains particles A, and the functional layer contains a binder resin and particles B.

[0039] The term "film roll" as used herein refers to a film having a functional layer provided on one side of a base film, which is wound into a roll.

[0040] The length of the film is not particularly limited, but is preferably a long film of 1000 m or more from the viewpoint of productivity, and is preferably within the range of 2000 to 5000 m from the viewpoints of productivity and handling. Similarly, the width of the film is preferably within the range of 1.3 to 4.0 m, and more preferably within the range of 1.5 to 3.0 m.

[0041] The "elastic modulus" defined in the present invention is synonymous with the "tensile elastic modulus" obtained by the following test method.

[0042] <Test method for tensile modulus> The film is cut into a size of 100 mm (MD) x 10 mm (TD) to obtain a test piece. This test piece is pulled in the MD (direction X) of the test piece in accordance with JIS K7127:1999 using an Orientec Tensilon RTC-1225A with a chuck distance of 50 mm, and the tensile modulus in the MD (direction X) is measured. The measurement was performed at 25°C and 55% RH. The unit is GPa.

[0043] The structure and effects of the film roll of the present invention will be described below with reference to the drawings.

[0044] 1A to 1E are schematic diagrams illustrating the functions of particles contained in a base film and a functional layer in a film roll.

[0045] FIG. 1A is a schematic diagram of a film roll having a base film and a functional layer formed by melt casting, as described in Japanese Patent No. 5594096.

[0046] The melt-formed base film 1 maintains a high resin density by being cooled after film formation. Next, a functional layer 6 containing anti-blocking particles B4 and a binder resin 5 is provided on the base film 1, and the film is wound into a roll shape to form a film roll 10.

[0047] Fig. 1B is an enlarged view of the film on the winding core of the film roll 10 shown in Fig. 1A. The winding core of the film roll 10 is subjected to high pressure due to the roll's own weight, but since the base film 1 maintains a high density, the repulsive force from the film side is strong, and the particles B4 on the functional layer 6 side do not sink into the base film 1 side but are exposed from the functional layer 6 side, ensuring anti-blocking properties.

[0048] FIG. 1C is a schematic diagram of a film roll having a base film and a functional layer formed by solution casting as a comparative example.

[0049] The substrate film 1 formed from the solution is dried after film formation to evaporate the solvent, forming minute gaps 2 inside, resulting in a relatively low resin density. Next, a functional layer 6 containing antiblocking particles B4 and a binder resin 5 is provided on the substrate film 1, and the film is wound into a roll shape as a film roll 10.

[0050] Fig. 1D is an enlarged view of the film on the core of the film roll 10 shown in Fig. 1C. As described above, the core of the film roll 10 is subjected to high pressure due to the roll's own weight, but since the base film 1 has minute gaps 2 inside and a relatively low density, the repulsive force from the film side is weak, and the particles B4 on the functional layer side sink into the base film 1 side. Therefore, the particles B exposed from the functional layer 6 decrease, and the anti-blocking property decreases.

[0051] FIG. 1E is a schematic diagram of a film roll of the present invention, which has a base film containing particles formed by solution casting and a functional layer.

[0052] The substrate film 1 formed from the solution is dried after film formation to evaporate the solvent, generating minute gaps 2 inside, but since the substrate film 1 itself contains particles A3, the minute gaps 2 are filled with the particles A3, maintaining an appropriate resin density. Next, a functional layer 6 containing anti-blocking particles B4 and a binder resin 5 is provided on the substrate film 1, and the film is wound into a roll shape as a film roll 10.

[0053] Fig. 1F is an enlarged view of the film on the winding core of the film roll 10 shown in Fig. 1E. As described above, the winding core of the film roll 10 is subjected to high pressure due to the roll's own weight, but the minute gaps 2 remaining inside the base film 1 are further filled with particles A3 by the application of pressure, so there is an appropriate repulsive force from the base film 1 side, and particles B4 on the functional layer 6 side do not sink into the base film 1 side but are exposed from the functional layer 6 side, ensuring anti-blocking properties.

[0054] FIG. 2 is a cross-sectional view of the film of the film roll of the present invention.

[0055] FIG. 2A is a cross-sectional view of a film showing the basic structure of a film roll of the present invention.

[0056] The base film 1 is formed containing particles A3, so that the particles A3 are exposed on the surface and unevenness is formed. When a functional layer 6 containing antiblocking particles B4 and binder resin 5 is formed on the base film 1, the particles A3 exposed from the base film 1 push up the particles B4 in the functional layer 6, and unevenness due to the particles B4 is formed on the surface of the functional layer 6. The unevenness formed at this time exhibits antiblocking properties, and at the same time, the particles B4 other than the unevenness are covered by the binder resin 5, so that it is possible to suppress the occurrence of scratches and the falling off of the particles due to contact between the particles and the film surface.

[0057] FIG. 2B is a cross-sectional view of a film showing a more preferred embodiment of the film roll of the present invention.

[0058] The base film 1 is formed containing the particles A3, and when the functional layer 6 containing the antiblocking particles B4 and the binder resin 5 is formed on the base film 1, the particles A3 exposed from the base film 1 push up the particles B4 in the functional layer 6, and the surface of the functional layer 6 is formed with unevenness due to the particles B. Furthermore, when the binder resin 5 used in the functional layer 6 is formed as a surface layer, that is, the coating film 7, without containing the particles B4, so as to cover the particles B4 that have formed the convex portions, the particles B4 are completely covered by the binder resin, and it becomes possible to further suppress the antiblocking property and the occurrence of scratches and the falling off of the particles due to contact between the particles and the film surface. The binder resin used in the coating film 7 may be the same as or different from the binder resin 5, and the functional layer may have two or more layers.

[0059] The components of the film roll of the present invention will be described below.

[0060] [1] Base film The base film according to the present invention is characterized in that the elastic modulus at 25° C. / 55% RH is within the range of 1.0 to 3.0 GPa, and the base film contains particles A.

[0061] In recent years, films for polarizing plate applications are required to be larger in area and thinner. In addition, it is desired that the physical properties and optical properties of protective films for protecting polarizing plates and retardation films for adjusting retardation do not change due to changes in the environment. Conventionally, cellulose materials with a relatively high elastic modulus such as triacetyl cellulose (commonly known as "TAC") were mainly used, but films containing materials with excellent water resistance such as cyclic olefin resins and acrylic resins have begun to be used as the protective films and retardation films. These resin films have a relatively low elastic modulus within the range of 1.0 to 3.0 GPa. Therefore, the configuration of the present invention is preferably applied to a base film using cycloolefin polymer (COP), which is a cyclic olefin resin, or polymethyl methacrylate (PMMA), which is an acrylic resin. However, the present invention is not limited to these, and it is sufficient that the elastic modulus of the film satisfies the above range.

[0062] In particular, since blocking is likely to occur when a film roll is formed from a low modulus film, for example, a resin having a modulus of elasticity of less than 3.0 GPa, it is effective to apply the configuration of the present invention to a film roll using a low modulus film, such as cycloolefin polymer (COP) or polymethyl methacrylate (PMMA), as the thermoplastic resin.

[0063] The effect of the present invention is more valuable in a thin film region where blocking is likely to occur. The thickness of the thin film is preferably in the range of 5 to 80 μm, more preferably in the range of 10 to 50 μm, and further preferably in the range of 10 to 45 μm.

[0064] [1.1] Thermoplastic resin The thermoplastic resin material used for the substrate film according to the present invention is not limited as long as it can be handled as a film roll after film formation. For example, thermoplastic resins used for polarizing plates include cellulose ester resins such as triacetyl cellulose (TAC), cellulose acetate propionate (CAP), and diacetyl cellulose (DAC), cyclic olefin resins such as cycloolefin polymers (hereinafter also referred to as COP or cycloolefin resins), polypropylene resins such as polypropylene (PP), acrylic resins such as polymethyl methacrylate (PMMA), and polyester resins such as polyethylene terephthalate (PET). Among these, from the viewpoints of optical properties including retardation and physical properties such as durability, cyclic olefin resins and acrylic resins are preferred.

[0065] [1.1.1] Cycloolefin resin The cycloolefin resin contained in the substrate film according to the present invention is preferably a polymer of a cycloolefin monomer, or a copolymer of a cycloolefin monomer and another copolymerizable monomer.

[0066] The cycloolefin monomer is preferably a cycloolefin monomer having a norbornene skeleton, and more preferably a cycloolefin monomer having a structure represented by the following general formula (A-1) or (A-2).

[0067] [ka]

[0068] In general formula (A-1), R 1 ~R 4 each independently represents a hydrogen atom, a hydrocarbon group having 1 to 30 carbon atoms, or a polar group, and p represents an integer of 0 to 2. 1 ~R 4 Not all of these represent hydrogen atoms at the same time, and R 1 and R 2 does not simultaneously represent a hydrogen atom, and R 3 and R 4 does not simultaneously represent a hydrogen atom.

[0069] In general formula (A-1), R 1 ~R 4 The hydrocarbon group having 1 to 30 carbon atoms represented by the formula (I) is preferably a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrocarbon group having 1 to 5 carbon atoms. The hydrocarbon group having 1 to 30 carbon atoms may further have a linking group containing, for example, a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, or a silicon atom. Examples of such linking groups include divalent polar groups such as a carbonyl group, an imino group, an ether bond, a silyl ether bond, and a thioether bond. Examples of the hydrocarbon group having 1 to 30 carbon atoms include a methyl group, an ethyl group, a propyl group, and a butyl group.

[0070] In general formula (A-1), R 1 ~R 4Examples of the polar group represented by the formula (I) include a carboxy group, a hydroxy group, an alkoxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amide group, and a cyano group. Among them, a carboxy group, a hydroxy group, an alkoxycarbonyl group, and an aryloxycarbonyl group are preferred, and an alkoxycarbonyl group and an aryloxycarbonyl group are preferred from the viewpoint of ensuring solubility during solution casting.

[0071] In terms of improving the heat resistance of the optical film, p in general formula (A-1) is preferably 1 or 2. When p is 1 or 2, the obtained polymer becomes bulky and the glass transition temperature is likely to be improved.

[0072] [ka]

[0073] In general formula (A-2), R 5 R represents a hydrogen atom, a hydrocarbon group having 1 to 5 carbon atoms, or an alkylsilyl group having an alkyl group having 1 to 5 carbon atoms. 6 represents a carboxy group, a hydroxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, an amino group, an amido group, a cyano group, or a halogen atom (a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom). p represents an integer of 0 to 2.

[0074] R in general formula (A-2) 5 preferably represents a hydrocarbon group having 1 to 5 carbon atoms, and more preferably represents a hydrocarbon group having 1 to 3 carbon atoms.

[0075] R in general formula (A-2) 6 preferably represents a carboxy group, a hydroxy group, an alkoxycarbonyl group or an aryloxycarbonyl group, and more preferably an alkoxycarbonyl group or an aryloxycarbonyl group from the viewpoint of ensuring solubility during solution casting.

[0076] In terms of improving the heat resistance of the optical film, p in general formula (A-2) preferably represents 1 or 2. When p represents 1 or 2, the obtained polymer becomes bulky and the glass transition temperature is likely to be improved.

[0077] Cycloolefin monomers having a structure represented by general formula (A-2) are preferred from the viewpoint of improving solubility in organic solvents. In general, by breaking the symmetry of an organic compound, the crystallinity is reduced, and the solubility in organic solvents is improved. R in general formula (A-2) 5 and R 6 is substituted only on the ring carbon atoms on one side of the axis of symmetry of the molecule, so that the molecular symmetry is low. In other words, a cycloolefin monomer having a structure represented by general formula (A-2) has high solubility and is therefore suitable for producing an optical film by a solution casting method.

[0078] The content ratio of the cycloolefin monomer having the structure represented by general formula (A-2) in the polymer of the cycloolefin monomer can be, for example, 70 mol% or more, preferably 80 mol% or more, more preferably 100 mol% based on the total of all the cycloolefin monomers constituting the cycloolefin resin. If the cycloolefin monomer having the structure represented by general formula (A-2) is contained at a certain level or more, the orientation of the resin is increased, so that the retardation value is likely to increase.

[0079] Specific examples of cycloolefin monomers having a structure represented by general formula (A-1) are shown in Exemplary Compounds 1 to 14 below, and specific examples of cycloolefin monomers having a structure represented by general formula (A-2) are shown in Exemplary Compounds 15 to 34 below.

[0080] [ka]

[0081] Examples of the copolymerizable monomer copolymerizable with the cycloolefin monomer include a copolymerizable monomer capable of ring-opening copolymerization with the cycloolefin monomer, and a copolymerizable monomer capable of addition copolymerization with the cycloolefin monomer.

[0082] Examples of copolymerizable monomers capable of ring-opening copolymerization include cycloolefins such as cyclobutene, cyclopentene, cycloheptene, cyclooctene, and dicyclopentadiene.

[0083] Examples of copolymerizable monomers capable of addition copolymerization include unsaturated double bond-containing compounds, vinyl cyclic hydrocarbon monomers, and (meth)acrylates. Examples of unsaturated double bond-containing compounds include olefin compounds having 2 to 12 carbon atoms (preferably 2 to 8), examples of which include ethylene, propylene, and butene. Examples of vinyl cyclic hydrocarbon monomers include vinylcyclopentene monomers such as 4-vinylcyclopentene and 2-methyl-4-isopropenylcyclopentene. Examples of (meth)acrylates include alkyl (meth)acrylates having 1 to 20 carbon atoms, such as methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate.

[0084] The content of the cycloolefin monomer in the copolymer of a cycloolefin monomer and a copolymerizable monomer can be, for example, 20 to 80 mol %, preferably 30 to 70 mol %, based on the total of all monomers constituting the copolymer.

[0085] As described above, the cycloolefin resin is a polymer obtained by polymerizing or copolymerizing a cycloolefin monomer having a norbornene skeleton, preferably a cycloolefin monomer having a structure represented by general formula (A-1) or (A-2), and examples thereof include the following:

[0086] (1) Ring-opening polymer of cycloolefin monomer (2) Ring-opening copolymers of cycloolefin monomers and copolymerizable monomers capable of ring-opening copolymerization with the cycloolefin monomers. (3) Hydrogenated product of the ring-opening (co)polymer of (1) or (2) above (4) A (co)polymer obtained by cyclizing the ring-opening (co)polymer of (1) or (2) above by the Friedel-Crafts reaction and then hydrogenating the same. (5) Saturated copolymers of cycloolefin monomers and compounds containing unsaturated double bonds (6) Addition copolymers of cycloolefin monomers with vinyl cyclic hydrocarbon monomers and their hydrogenated products (7) Alternating copolymer of cycloolefin monomer and (meth)acrylate The polymers (1) to (7) can be obtained by known methods, for example, the methods described in JP-A-2008-107534 and JP-A-2005-227606. For example, the catalyst and solvent used in the ring-opening copolymerization (2) can be those described in paragraphs 0019 to 0024 of JP-A-2008-107534. The catalyst used in the hydrogenation (3) and (6) can be those described in paragraphs 0025 to 0028 of JP-A-2008-107534. The acidic compound used in the Friedel-Crafts reaction (4) can be those described in paragraph 0029 of JP-A-2008-107534. The catalysts used in the addition polymerizations (5) to (7) above can be those described in, for example, paragraphs 0058 to 0063 of JP-A No. 2005-227606. The alternating copolymerization reaction (7) above can be carried out, for example, by the method described in paragraphs 0071 and 0072 of JP-A No. 2005-227606.

[0087] Among them, the polymers of (1) to (3) and (5) are preferred, and the polymers of (3) and (5) are more preferred. That is, the cycloolefin resin preferably contains at least one of the structural units represented by the following general formula (B-1) and the structural units represented by the following general formula (B-2), and more preferably contains only the structural unit represented by the general formula (B-2) or contains both the structural unit represented by the general formula (B-1) and the structural unit represented by the general formula (B-2). The structural unit represented by the general formula (B-1) is a structural unit derived from the cycloolefin monomer represented by the above-mentioned general formula (A-1), and the structural unit represented by the general formula (B-2) is a structural unit derived from the cycloolefin monomer represented by the above-mentioned general formula (A-2).

[0088] [ka]

[0089] In the general formula (B-1), X represents -CH=CH- or -CH2CH2-. 1 ~R 4 and p are each R in general formula (A-1). 1 ~R 4 and p.

[0090] [ka]

[0091] In the general formula (B-2), X represents -CH=CH- or -CH2CH2-. 5 ~R 6 and p are each R in general formula (A-2). 5 ~R 6 and p.

[0092] The cycloolefin resin according to the present invention may be a commercially available product. Examples of commercially available cycloolefin resins include Arton G (e.g., G7810, etc.), Arton F, Arton R (e.g., R4500, R4900, and R5000, etc.), and Arton RX, all of which are manufactured by JSR Corporation.

[0093] The intrinsic viscosity [η]inh of the cycloolefin resin is preferably 0.2 to 5 cm3 / g, and more preferably 0.3 to 3 cm3 / g, when measured at 30°C. 3 / g is more preferable, and 0.4 to 1.5 cm 3 It is more preferable that the molecular weight is / g.

[0094] The number average molecular weight (Mn) of the cycloolefin resin is preferably 8,000 to 100,000, more preferably 10,000 to 80,000, and even more preferably 12,000 to 50,000. The weight average molecular weight (Mw) of the cycloolefin resin is preferably 20,000 to 300,000, more preferably 30,000 to 250,000, and even more preferably 40,000 to 200,000. The number average molecular weight and weight average molecular weight of the cycloolefin resin can be measured in polystyrene equivalent terms by gel permeation chromatography (GPC).

[0095] <Gel permeation chromatography> Solvent: Methylene chloride Column: Shodex K806, K805, K803G (Showa Denko K.K., three columns connected together) Column temperature: 25℃ Sample concentration: 0.1% by mass Detector: RI Model 504 (GL Sciences) Pump: L6000 (Hitachi, Ltd.) Flow rate: 1.0ml / min Calibration curve: A calibration curve was used using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) in the range of Mw=500 to 2,800,000. It is preferable to use the 13 samples at approximately equal intervals.

[0096] When the intrinsic viscosity [η]inh, number average molecular weight and weight average molecular weight are within the above ranges, the cycloolefin resin has good heat resistance, water resistance, chemical resistance, mechanical properties and moldability into a film.

[0097] The glass transition temperature (Tg) of the cycloolefin resin is usually 110° C. or higher, preferably 110 to 350° C., more preferably 120 to 250° C., and even more preferably 120 to 220° C. If the Tg is 110° C. or higher, deformation under high temperature conditions is easily suppressed. On the other hand, if the Tg is 350° C. or lower, molding is easy and deterioration of the resin due to heat during molding is also easily suppressed.

[0098] The content of the cycloolefin resin is preferably 70% by mass or more, and more preferably 80% by mass or more, based on the mass of the film.

[0099] [1.1.2] Acrylic resins The acrylic resin according to the present invention is a polymer of an acrylic acid ester or a methacrylic acid ester, and also includes copolymers with other monomers.

[0100] Therefore, the acrylic resin according to the present invention also includes methacrylic resin. Although there is no particular limitation on the resin, it is preferable that the resin contains 50 to 99% by mass of methyl methacrylate units and 1 to 50% by mass of other monomer units copolymerizable therewith.

[0101] Other units constituting the acrylic resin formed by copolymerization include alkyl methacrylates having an alkyl number of 2 to 18 carbon atoms, alkyl acrylates having an alkyl number of 1 to 18 carbon atoms, hydroxyalkyl acrylates such as isobornyl methacrylate and 2-hydroxyethyl acrylate, α,β-unsaturated acids such as acrylic acid and methacrylic acid, acrylamides such as acryloylmorpholine and N-hydroxyphenylmethacrylamide, unsaturated group-containing dicarboxylic acids such as N-vinylpyrrolidone, maleic acid, fumaric acid, and itaconic acid, aromatic vinyl compounds such as styrene and α-methylstyrene, α,β-unsaturated nitriles such as acrylonitrile and methacrylonitrile, maleic anhydride, maleimide, N-substituted maleimide, glutarimide, and glutaric anhydride.

[0102] Examples of copolymerizable monomers forming units other than glutarimide and glutaric anhydride from the above units include monomers corresponding to the above units, such as alkyl methacrylates having an alkyl number of 2 to 18 carbon atoms, alkyl acrylates having an alkyl number of 1 to 18 carbon atoms, isobornyl methacrylate, hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate, α,β-unsaturated acids such as acrylic acid and methacrylic acid, acrylamides such as acryloylmorpholine and N-hydroxyphenylmethacrylamide, unsaturated group-containing divalent carboxylic acids such as N-vinylpyrrolidone, maleic acid, fumaric acid, and itaconic acid, aromatic vinyl compounds such as styrene and α-methylstyrene, α,β-unsaturated nitriles such as acrylonitrile and methacrylonitrile, maleic anhydride, maleimide, and N-substituted maleimide.

[0103] Furthermore, the glutarimide unit can be formed, for example, by reacting an intermediate polymer having a (meth)acrylic acid ester unit with a primary amine (imidizing agent) to effect imidization (see JP-A-2011-26563).

[0104] The glutaric anhydride units can be formed, for example, by heating an intermediate polymer having (meth)acrylic ester units (see Japanese Patent No. 4961164).

[0105] Of the above-mentioned structural units, it is particularly preferable that the acrylic resin according to the present invention contains isobornyl methacrylate, acryloylmorpholine, N-hydroxyphenylmethacrylamide, N-vinylpyrrolidone, styrene, hydroxyethyl methacrylate, maleic anhydride, maleimide, N-substituted maleimide, glutaric anhydride, or glutarimide, from the viewpoint of mechanical strength.

[0106] The acrylic resin according to the present invention preferably has a weight average molecular weight (Mw) in the range of 50,000 to 1,000,000, more preferably in the range of 100,000 to 1,000,000, and particularly preferably in the range of 200,000 to 800,000, from the viewpoints of controlling dimensional changes due to changes in the environmental temperature and humidity atmosphere, and of improving peelability from metal supports during film production, drying properties from organic solvents, heat resistance, and mechanical strength.

[0107] If it is 50,000 or more, the heat resistance and mechanical strength are excellent, and if it is 1,000,000 or less, the peelability from the metal support and the drying property of the organic solvent are excellent.

[0108] The method for producing the acrylic resin according to the present invention is not particularly limited, and any of the known methods such as suspension polymerization, emulsion polymerization, bulk polymerization, or solution polymerization may be used. Here, as the polymerization initiator, a normal peroxide-based or azo-based one can be used, and a redox-based one can also be used. The polymerization temperature can be within the range of 30 to 100°C in suspension or emulsion polymerization, and within the range of 80 to 160°C in bulk or solution polymerization. In order to control the reduced viscosity of the obtained copolymer, the polymerization can also be carried out using an alkyl mercaptan or the like as a chain transfer agent.

[0109] The glass transition temperature Tg of the acrylic resin is preferably within the range of 80 to 120° C. from the viewpoint of maintaining the mechanical strength of the film.

[0110] The acrylic resin according to the present invention may be a commercially available product. For example, Delpet 60N, 80N, 980N, SR8200 (all manufactured by Asahi Kasei Chemicals Corporation), Dianale BR52, BR80, BR83, BR85, BR88, EMB-143, EMB-159, EMB-160, EMB-161, EMB-218, EMB-229, EMB-270, EMB-273 (all manufactured by Mitsubishi Rayon Co., Ltd.), KT75, TX400S, IPX012 (all manufactured by Denki Kagaku Kogyo Co., Ltd.), etc. Two or more types of acrylic resins may be used in combination.

[0111] The acrylic resin according to the present invention preferably contains an additive, and an example of the additive is acrylic particles (rubber elastomer particles) described in International Publication No. 2010 / 001668, which are preferably contained in order to improve the mechanical strength of the film and adjust the dimensional change rate. Examples of commercially available products of such multilayered acrylic granular composites include "Metabrene W-341" manufactured by Mitsubishi Rayon Co., Ltd., "Kane Ace" manufactured by Kaneka Corporation, "Paraloid" manufactured by Kureha Corporation, "Acryloid" manufactured by Rohm and Haas Co., Ltd., "Staphyloid" manufactured by Aica Corporation, Chemisnow MR-2G, MS-300X (all manufactured by Soken Chemical & Engineering Co., Ltd.), and "Parapet SA" manufactured by Kuraray Co., Ltd., and these can be used alone or in combination.

[0112] The volume average particle size of the acrylic particles is 0.35 μm or less, preferably 0.01 to 0.35 μm, and more preferably 0.05 to 0.30 μm. If the particle size is a certain level or more, the film can be easily stretched under heating, and if the particle size is a certain level or less, the transparency of the obtained film is not easily impaired.

[0113] From the viewpoint of flexibility, the substrate film according to the present invention preferably has a flexural modulus (JIS K7171) of 1.5 GPa or less. This flexural modulus is more preferably 1.3 GPa or less, and even more preferably 1.2 GPa or less. This flexural modulus varies depending on the type and amount of the acrylic resin and rubber elastomer particles in the film, and for example, the higher the content of the rubber elastomer particles, the smaller the flexural modulus generally becomes. Furthermore, the flexural modulus generally becomes smaller when a copolymer of alkyl methacrylate and alkyl acrylate is used as the acrylic resin than when a homopolymer of alkyl methacrylate is used.

[0114] [1.1.3] Cellulose ester resin In the film roll of the present invention, a cellulose ester resin may be used whose elastic modulus falls within the range of the present invention by adjusting additives and the like.

[0115] The cellulose ester used in the present invention refers to a cellulose acylate resin in which some or all of the hydrogen atoms of the hydroxyl groups (-OH) at the 2nd, 3rd and 6th positions in the β-1,4-bonded glucose units constituting cellulose are substituted with acyl groups.

[0116] The cellulose ester used is not particularly limited, but is preferably an ester of a linear or branched carboxylic acid having about 2 to 22 carbon atoms. The carboxylic acid constituting the ester may be an aliphatic carboxylic acid, may form a ring, or may be an aromatic carboxylic acid. For example, cellulose esters in which the hydrogen atom of the hydroxyl group of cellulose is substituted with an acyl group having 2 to 22 carbon atoms, such as an acetyl group, a propionyl group, a butyryl group, an isobutyryl group, a valeryl group, a pivaloyl group, a hexanoyl group, an octanoyl group, a lauroyl group, or a stearoyl group, may be mentioned. The carboxylic acid (acyl group) constituting the ester may have a substituent. The carboxylic acid constituting the ester is preferably a lower fatty acid having 6 or less carbon atoms, and more preferably a lower fatty acid having 3 or less carbon atoms. The acyl group in the cellulose ester may be a single type or a combination of multiple acyl groups.

[0117] Specific examples of preferred cellulose esters include cellulose acetates such as diacetyl cellulose (DAC) and triacetyl cellulose (TAC), as well as mixed fatty acid esters of cellulose to which a propionate group or a butyrate group is bonded in addition to an acetyl group, such as cellulose acetate propionate (CAP), cellulose acetate butyrate, and cellulose acetate propionate butyrate. These cellulose esters may be used alone or in combination.

[0118] (Type of acyl group / degree of substitution) By adjusting the type and substitution degree of the acyl group of the cellulose ester, the humidity fluctuation of the retardation can be controlled within a desired range, and the uniformity of the film thickness can be improved.

[0119] The smaller the degree of substitution of the acyl group in the cellulose ester, the more improved the retardation is, and thus the thinner the film can be formed.On the other hand, if the degree of substitution of the acyl group is too small, the durability may be deteriorated, which is not preferable.

[0120] On the other hand, the higher the substitution degree of the acyl group of the cellulose ester, the less the retardation is expressed, so it is necessary to increase the stretching ratio during film formation, but it is difficult to stretch uniformly at a high stretching ratio, which results in a large (worsening) variation in film thickness. In addition, the Rt humidity fluctuation, which is the retardation in the thickness direction (retardation), occurs when water molecules coordinate to the carbonyl group of cellulose, so the higher the substitution degree of the acyl group, i.e., the more carbonyl groups there are in the cellulose, the worse the Rt humidity fluctuation tends to be.

[0121] The total degree of substitution of the cellulose ester is preferably in the range of 2.1 to 2.5. By setting it in this range, environmental fluctuations (especially Rt fluctuations due to humidity) can be suppressed and the uniformity of the film thickness can be improved. More preferably, it is in the range of 2.2 to 2.45 from the viewpoint of improving the flowability and stretchability during film formation and further improving the uniformity of the film thickness.

[0122] More specifically, the cellulose ester satisfies both of the following formulae (a) and (b): wherein X is the degree of substitution of the acetyl group, and Y is the degree of substitution of the propionyl group or the butyryl group, or the degree of substitution of a mixture thereof. Formula (a): 2.1≦X+Y≦2.5 Formula (b): 0≦Y≦1.5

[0123] The cellulose ester is preferably cellulose acetate (Y=0) and cellulose acetate propionate (CAP) (Y; propionyl group, Y>0), and more preferably cellulose acetate with Y=0 from the viewpoint of reducing film thickness variation. The cellulose acetate that is particularly preferably used is cellulose diacetate (DAC) with 2.1≦X≦2.5 (more preferably 2.15≦X≦2.45) from the viewpoint of setting retardation expression, Rt humidity fluctuation, and film thickness variation within the desired range. In addition, when Y>0, the cellulose acetate propionate (CAP) that is particularly preferably used is 0.95≦X≦2.25, 0.1≦Y≦1.2, and 2.15≦X+Y≦2.45.

[0124] By using the above-mentioned cellulose acetate or cellulose acetate propionate, a film roll having excellent retardation, mechanical strength, and resistance to environmental changes can be obtained.

[0125] The degree of substitution of acyl groups indicates the average number of acyl groups per glucose unit, and indicates how many hydrogen atoms of hydroxyl groups at the 2nd, 3rd and 6th positions of one glucose unit are substituted with acyl groups. Therefore, the maximum degree of substitution is 3.0, which means that all hydrogen atoms of hydroxyl groups at the 2nd, 3rd and 6th positions are substituted with acyl groups. These acyl groups may be substituted evenly at the 2nd, 3rd and 6th positions of the glucose unit, or may be substituted with a distribution. The degree of substitution is determined by the method specified in ASTM-D817-96.

[0126] To obtain desired optical properties, cellulose acetates having different degrees of substitution may be mixed and used. The mixing ratio of different cellulose acetates is not particularly limited.

[0127] The number average molecular weight (Mn) of cellulose ester is 2×10 4 ~3×10 5 range, and even 2×10 4 ~1.2×10 5 range, and even 4×10 4 ~8×10 4 Within this range, the mechanical strength of the resulting film roll is increased, which is preferable.

[0128] The number average molecular weight Mn of the cellulose ester is calculated by measurement using gel permeation chromatography (GPC) under the above-mentioned measurement conditions.

[0129] The weight average molecular weight (Mw) of the cellulose ester is 2×10 4 ~1×10 6 range, and even 2×10 4 ~1.2×10 5 range, or even 4×10 4 ~8×10 4Within this range, the mechanical strength of the resulting film roll is increased, which is preferable.

[0130] The raw cellulose for the cellulose ester is not particularly limited, but examples thereof include cotton linters, wood pulp, kenaf, etc. Furthermore, the cellulose esters obtained from these can be mixed and used in any desired ratio.

[0131] Cellulose esters such as cellulose acetate and cellulose acetate propionate can be produced by known methods. In general, raw cellulose is mixed with a specific organic acid (acetic acid, propionic acid, etc.), an acid anhydride (acetic anhydride, propionic anhydride, etc.), and a catalyst (sulfuric acid, etc.) to esterify the cellulose, and the reaction is continued until a cellulose triester is produced. In the triester, the three hydroxyl groups of the glucose unit are replaced with the acyl acid of the organic acid.

[0132] If two kinds of organic acids are used at the same time, mixed ester type cellulose esters, such as cellulose acetate propionate and cellulose acetate butyrate, can be prepared. Then, the cellulose triester is hydrolyzed to synthesize a cellulose ester resin having a desired degree of acyl substitution. After that, the cellulose ester resin is completed through processes such as filtration, precipitation, washing with water, dehydration, and drying. Specifically, the synthesis can be performed by referring to the method described in JP-A-10-45804.

[0133] [1.1.4] Particle A As described above, particles A (fine particles usually called "matting agents") are added to the base film of the present invention from the viewpoint of antiblocking properties and preventing the particles B of the functional layer from falling off.

[0134] The particles A may be either an inorganic compound or an organic compound as long as it does not impair the transparency of the resulting film roll and has heat resistance during melt film formation. These particles A may be used alone or in combination of two or more kinds.

[0135] By combining particles with different particle sizes and shapes (e.g., needle-shaped and spherical), it is possible to achieve both high levels of transparency and lubricity.

[0136] Among these, silicon dioxide (silica particles) is particularly preferably used because it has a refractive index close to those of the cycloolefin resin, acrylic resin, and cellulose ester resin and therefore has excellent transparency (haze).

[0137] Specific examples of silicon dioxide include Aerosil (registered trademark) 200V, Aerosil (registered trademark) R972V, Aerosil (registered trademark) R972, R974, R812, 200, 300, R202, OX50, TT600, NAX50 (all manufactured by Nippon Aerosil Co., Ltd.), Sea Hoster (registered trademark) KEP-10, Sea Hoster (registered trademark) KEP-30, Sea Hoster (registered trademark) KEP-50 (all manufactured by Nippon Shokubai Co., Ltd.), Silo Hobic (registered trademark) 100 (manufactured by Fuji Silysia Co., Ltd.), Nipsil (registered trademark) E220A (manufactured by Nippon Silica Kogyo Co., Ltd.), and Adma Fine (registered trademark) SO (manufactured by Admatechs Co., Ltd.).

[0138] The shape of the particles is not particularly limited and may be any shape, such as amorphous, acicular, flat, or spherical. In particular, spherical particles are preferred because they can provide a film roll with good transparency.

[0139] The particle size is preferably smaller than the wavelength of visible light, and more preferably 1 / 2 or less of the wavelength of visible light, since light scattering occurs when the particle size is close to the wavelength of visible light, resulting in poor transparency. If the particle size is too small, the slipperiness may not be improved, so the number-average particle size of the primary particles is preferably in the range of 5 to 20 nm. Note that the particle size means the size of the aggregate when the particle is an aggregate of primary particles. Furthermore, when the particle is not spherical, it means the diameter of a circle equivalent to the projected area of ​​the particle.

[0140] The particles A are added in an amount of 0.05 to 10% by mass, preferably 0.1 to 5% by mass, and particularly preferably 0.1 to 1% by mass, based on the base resin.

[0141] From the viewpoints of antiblocking property, suppression of particle dropout, and transparency, it is preferable that the number average particle diameter of the primary particles of the particle A is within a range of 5 to 20 nm, and the ratio R (RB / RA) of the number average particle diameter (RB) of the primary particles of the particle B described below to the number average particle diameter (RA) of the primary particles of the particle A is within a range of 2.5 to 100.

[0142] (Method of measuring number average particle size) The number average particle size of the silica particles can be measured as follows.

[0143] A 30,000-fold magnification photograph of each particle A or particle B was taken using a scanning electron microscope, and the photographic image was captured using a scanner. The photographic image of particle A or particle B was binarized using an image processing and analysis device LUZEX AP (manufactured by Nireco Corporation), the horizontal Feret diameters of 100 particles were calculated, and the average value was taken as the number-average particle diameter.

[0144] From the viewpoint of dispersibility, the particles A may be surface-modified with a surface modifier. In particular, it is preferable that the hydrophobicity is adjusted with the following silane coupling agent.

[0145] (Silane coupling agent) Examples of the silane coupling agent include isocyanate group-containing alkoxysilanes such as γ-isocyanate propyl trimethoxysilane, γ-isocyanate propyl triethoxysilane, γ-isocyanate propyl methyl diethoxysilane, and γ-isocyanate propyl methyl dimethoxysilane; γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-aminopropyl methyl dimethoxysilane, γ-aminopropyl methyl diethoxysilane, and γ-(2-aminoethyl)aminopropyl trimethoxysilane. amino group-containing alkoxysilanes such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-ureidopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, N-benzyl-γ-aminopropyltrimethoxysilane, and N-vinylbenzyl-γ-aminopropyltriethoxysilane; γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, mercapto group-containing alkoxysilanes such as γ-mercaptopropyltriethoxysilane, γ-mercaptopropylmethyldimethoxysilane, γ-mercaptopropylmethyldiethoxysilane; epoxy group-containing alkoxysilanes such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltriethoxysilane; carboxy-containing alkoxysilanes such as N-β-(carboxymethyl)aminoethyl-γ-aminopropyltrimethoxysilane; vinyl-type unsaturated group-containing alkoxysilanes such as vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloyloxypropylmethyldimethoxysilane, γ-acroyloxypropylmethyltriethoxysilane; halogen group-containing alkoxysilanes such as γ-chloropropyltrimethoxysilane;These include isocyanate group-containing alkoxysilanes such as tris(trimethoxysilyl)isocyanate, amino-modified silyl polymers, silylated amino polymers, unsaturated aminosilane complexes, phenylamino long-chain alkylsilanes, aminosilylated silicones, silylated polyesters, and derivatives thereof;

[0146] [1.1.5] Other additives The film roll of the present invention may contain the following additives in addition to the above-mentioned thermoplastic resin.

[0147] (a) Plasticizer The film roll of the present invention preferably contains at least one plasticizer for the purpose of imparting processability to, for example, a polarizing plate protective film, etc. The plasticizers are preferably used alone or in combination of two or more kinds.

[0148] Among the plasticizers, it is preferable to contain at least one plasticizer selected from the group consisting of polyesters, sugar esters, and styrene-based compounds, from the viewpoint of effectively controlling moisture permeability and achieving high compatibility with the base resin. Among them, it is preferable to contain polyester as the plasticizer.

[0149] From the viewpoint of achieving both improved wet heat resistance and compatibility with the base resin, the plasticizer preferably has a molecular weight of 15,000 or less, more preferably 10,000 or less. When the compound having a molecular weight of 10,000 or less is a polymer, the weight average molecular weight (Mw) is preferably 10,000 or less. The weight average molecular weight (Mw) is preferably in the range of 100 to 10,000, more preferably 400 to 8,000.

[0150] In particular, in order to obtain the effects of the present invention, the compound having a molecular weight of 2000 or less is preferably contained in an amount within the range of 1 to 40 parts by mass, more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the base resin. By containing the compound within the above range, it is possible to effectively control the moisture permeability and to ensure compatibility with the base resin, which is preferable.

[0151] <polyester> The polyester is an esterified product that can be obtained by an esterification reaction or an ester exchange reaction between a dicarboxylic acid compound and a diol compound, and both ends of the polyester may or may not be capped.

[0152] The film roll of the present invention may contain, as the polyester, one type of compound or a mixture of two or more types of compounds having different chemical structures or molecular weights.

[0153] For example, a mixture of two or more compounds having different chemical structures or molecular weights may be produced by synthesizing a polyester using a plurality of different types of raw materials, or by synthesizing a plurality of polyesters having a single structure or molecular weight and then mixing the plurality of polyesters.

[0154] In this case, two or more compounds having different chemical structures or molecular weights may be mixed and then added to a dope for producing a substrate film, or one type of compound may be added to a dope and then another type of compound may be added to the dope.

[0155] The polyester can be synthesized by a conventional method, either by a thermal melt condensation method using an esterification reaction or transesterification reaction of a dicarboxylic acid compound, a diol compound, and, if necessary, a monocarboxylic acid or monoalcohol for end-capping, or by an interfacial condensation method between a dicarboxylic acid compound and an acid chloride of a monocarboxylic acid for end-capping with a diol compound.

[0156] The structure of the polyester can be adjusted by the types of the dicarboxylic acid compound and diol compound used as the raw materials, the types of the monoalcohol compound and monocarboxylic acid compound used as the end-capping agent, and the amount of the raw material compound added. The weight-average molecular weight of the polyester can be adjusted by the pressure, temperature, and reaction time during the ester polymerization reaction, the addition ratio of the dicarboxylic acid compound and diol compound used as the raw materials, the addition time and amount of the end-capping agent, etc.

[0157] The weight average molecular weight of the polyester used in the present invention can be measured by gel permeation chromatography under the following conditions.

[0158] Solvent: Dichloromethane Column: Shodex K806, K805, K803G (three columns made by Showa Denko Co., Ltd. were used in combination) Column temperature: 25℃ Sample concentration: 0.1% by mass Detector: RI Model 504 (GL Sciences) Pump: L6000 (Hitachi, Ltd.) Flow rate: 1.0ml / min Calibration curve: A calibration curve was used using 13 samples of standard polystyrene STK standard polystyrene (manufactured by Tosoh Corporation) with Mw=500 to 2,800,000. It is preferable to use the 13 samples at approximately equal intervals.

[0159] (b) Optional components The film roll of the present invention may contain other optional components such as antioxidants, colorants, UV absorbers, acrylic particles, hydrogen-bonding solvents, ionic surfactants, etc. These components may be added in the range of 0.01 to 20 parts by mass per 100 parts by mass of the base resin.

[0160] <Antioxidants> In the film roll of the present invention, generally known antioxidants can be used, and in particular, lactone-based, sulfur-based, phenol-based, double bond-based, hindered amine-based, and phosphorus-based compounds can be preferably used.

[0161] These antioxidants are added in an amount of 0.05 to 20% by mass, preferably 0.1 to 1% by mass, based on the resin, which is the main raw material of the film. A synergistic effect can be obtained by using several different types of compounds in combination, rather than using only one type of these antioxidants. For example, it is preferable to use lactone-based, phosphorus-based, phenol-based and double bond-based compounds in combination.

[0162] <Coloring Agent> The film roll of the present invention preferably contains a colorant for adjusting the color tone within a range that does not impair the effects of the present invention. The colorant means a dye or a pigment, and in the present invention, refers to a colorant having an effect of making the color tone of the liquid crystal screen blue, adjusting the yellow index, or reducing haze.

[0163] As the colorant, various dyes and pigments can be used, and anthraquinone dyes, azo dyes, phthalocyanine pigments, etc. are effective.

[0164] <Ultraviolet absorber> Since the film roll of the present invention can be used on the viewing side or backlight side of a polarizing plate, it may contain an ultraviolet absorbing agent for the purpose of imparting an ultraviolet absorbing function.

[0165] The ultraviolet absorbing agent is not particularly limited, but examples thereof include ultraviolet absorbing agents of benzotriazole type, 2-hydroxybenzophenone type, salicylic acid phenyl ester type, etc. For example, triazoles such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, etc., and benzophenones such as 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2,2′-dihydroxy-4-methoxybenzophenone, etc. can be exemplified.

[0166] The above ultraviolet absorbents can be used alone or in combination of two or more.

[0167] The amount of the ultraviolet absorber used varies depending on the type of ultraviolet absorber, the conditions of use, etc., but is generally added in the range of 0.05 to 10% by mass, preferably 0.1 to 5% by mass, based on the base resin.

[0168] [2] Functional layer The functional layer according to the present invention is characterized by containing a binder resin and particles B.

[0169] [2.1] Binder resin <About the main ingredients> The functional layer preferably contains a resin having an organic reactive group, such as an amide-based resin, an epoxy-based resin, an isocyanate-based resin, a urethane-based resin, or a polyolefin-based resin.

[0170] Among these, the functional layer preferably contains a polyolefin-based resin, an amide-based resin, or a urethane-based resin as a binder, and more preferably contains a polyolefin-based resin, in order to satisfactorily enhance adhesion to the base film.

[0171] <Polyolefin Resin> Examples of polyolefin resins that can be used include polyethylene, polypropylene, ethylene-propylene copolymers, random copolymers or block copolymers (e.g., ethylene-propylene-butene copolymers) of ethylene and / or propylene with other comonomers (e.g., 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, α-olefin comonomers having 2 to 6 carbon atoms). Also usable are copolymers of two or more of the above other comonomers and mixtures of two or more of the above polymers.

[0172] The polyolefin resin may be a modified polyolefin such as a polyolefin modified with an unsaturated carboxylic acid and / or an acid anhydride. The modified polyolefin is preferably a polyolefin modified with an unsaturated carboxylic acid and / or an acid anhydride and / or a compound having one or more double bonds per molecule.

[0173] Examples of the unsaturated carboxylic acid and acid anhydride include α,β-unsaturated carboxylic acids and their anhydrides such as maleic acid, maleic anhydride, fumaric acid, citraconic acid, citraconic anhydride, mesaconic acid, itaconic acid, itaconic anhydride, aconitic acid, aconitic anhydride, etc. These may be used alone or in combination of two or more kinds.

[0174] Examples of compounds having one or more double bonds per molecule include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, Examples of the acrylates include 2-hydroxybutyl (meth)acrylate, benzyl (meth)acrylate, glycidyl (meth)acrylate, (meth)acrylic acid, (di)ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin di(meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and acrylamide. Note that "(meth)acrylic acid" refers to acrylic acid and methacrylic acid. It is a general term for either or both of these.

[0175] In addition to the above compounds having a double bond, styrene, α-methylstyrene, paramethylstyrene, chloromethylstyrene, divinylbenzene, vinyl acetate, and vinyl ester of versatic acid can also be used.

[0176] The modified polyolefin can be obtained by dissolving a polyolefin in an organic solvent such as toluene or xylene, and reacting it with an α,β-unsaturated carboxylic acid and / or its acid anhydride and / or a compound having one or more double bonds per molecule in the presence of a radical generator, or by reacting it with an α,β-unsaturated carboxylic acid and / or its acid anhydride and / or a compound having one or more double bonds per molecule in the presence or absence of a radical generator in an autoclave that can be heated to a temperature above the softening temperature or melting point of the polyolefin, or in a single-screw or twin-screw or more multi-screw extruder in which the reaction can be carried out in a molten state.

[0177] Examples of the radical generator that can be used in the reaction to obtain the modified polyolefin include peroxides such as di-tert-butyl perphthalate, tert-butyl hydroperoxide, dicumyl peroxide, benzoyl peroxide, tert-butyl peroxybenzoate, tert-butyl peroxyethylhexanoate, tert-butyl peroxypivalate, methyl ethyl ketone peroxide, and di-tert-butyl peroxide; and azonitriles such as azobisisobutyronitrile and azobisisopropionitrile. When the peroxide is used to carry out graft copolymerization, the content of the peroxide is preferably 0.1 to 50.0 parts by mass, more preferably 0.5 to 30.0 parts by mass, based on the polyolefin.

[0178] The polyolefin resin may be one produced by a known method, and there are no particular limitations on the production method or degree of modification.

[0179] The polyolefin resin preferably has a weight average molecular weight (Mw) of 20,000 to 100,000. When the weight average molecular weight (Mw) of the polyolefin resin is 20,000 or more, the cohesive force of the image (coating film) formed on the surface of a low absorbent substrate or a non-absorbent substrate is increased, improving the adhesion of the coating film. When the weight average molecular weight (Mw) is 100,000 or less, the solubility in organic solvents is good, and the particle size of the emulsion dispersion is promoted to be reduced. The weight average molecular weight (Mw) is a value measured by gel permeation chromatography (GPC).

[0180] The polyolefin resin may be a commercially available product. Examples of commercially available polyolefin resins include Arrowbase SB-1200, Arrowbase SE1030N (manufactured by Unitika Ltd., "Arrowbase" is a registered trademark of the company), Auroren 150A, Auroren AE-301 (manufactured by Nippon Paper Industries Co., Ltd., "Auroren" is a registered trademark of the company), Superclone E-415 (manufactured by Nippon Paper Industries Co., Ltd., "Superclone" is a registered trademark of the company), and Hardlen Na-1001 (manufactured by Toyobo Co., Ltd., and "Hardlen" is a registered trademark of the company).

[0181] Amide Resin The amide resin is preferably a water-soluble polyamide epoxy resin, which is obtained by reacting a condensation polymer of a polyamine and a polycarboxylic acid with an epihalohydrin.

[0182] The polyamine is an amine having three or more functional groups, preferably a trifunctional amine. The polyamine is preferably an aliphatic polyamine. The polycarboxylic acid is a carboxylic acid having two or more functional groups, preferably a bifunctional carboxylic acid. The polycarboxylic acid is preferably an aliphatic polycarboxylic acid. The epihalohydrin is preferably epichlorohydrin.

[0183] Examples of commercially available water-soluble polyamide epoxy resins include Sumirez Resin (registered trademark) 6615, 650(30), and 675A manufactured by Taoka Chemical Co., Ltd., the WS series manufactured by Seiko PMC Corporation, and Arafix 530 and 504 manufactured by Arakawa Chemical Industries, Ltd.

[0184] <Urethane resin> The urethane resin contains repeating units derived from a reaction product between (i) a polyhydric alcohol component and (ii) a polyhydric isocyanate component.

[0185] (i) Examples of the polyhydric alcohol component include polyol compounds, polyether polyols, polyester polyols, polyether ester polyols, and polycarbonate polyols. These polyhydric alcohol components may be used alone or in combination of two or more.

[0186] Examples of the polyol compound include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, tricyclodecane dimethanol, 1,4-cyclohexane dimethanol, 2,2-dimethylpropanediol, 1,4-butanediol, and the like.

[0187] Examples of polyether polyols include alkylene oxide adducts of the above-mentioned polyol compounds; ring-opening (co)polymers of alkylene oxides and cyclic ethers (e.g., tetrahydrofuran); polyethylene glycol, polypropylene glycol, ethylene glycol-propylene glycol copolymers; glycols, polytetramethylene glycol, and other glycols. Examples of polyester polyols include those obtained by polycondensing dicarboxylic acids such as adipic acid, succinic acid, sebacic acid, glutaric acid, maleic acid, fumaric acid, phthalic acid, and other anhydrides with polyol compounds such as ethylene glycol and propylene glycol under conditions of excess hydroxyl groups. Examples of polyether ester polyols include polytetramethylene glycol-adipic acid condensates.

[0188] Examples of polycarbonate polyols include compounds represented by the general formula: HO-R-(OC(O)-OR)x-OH (R represents a saturated fatty acid polyol residue having 1 to 12 carbon atoms, and x represents the number of repeating units in the molecule and is an integer of 5 to 50).

[0189] (ii) Examples of the polyisocyanate component include aliphatic, alicyclic, or aromatic compounds containing two or more isocyanate groups in one molecule. The aliphatic diisocyanate compound is preferably an aliphatic diisocyanate having 1 to 12 carbon atoms, examples of which include hexamethylene diisocyanate, 2,2,4-trimethylhexane diisocyanate, and hexane diisocyanate (HDI). The alicyclic diisocyanate compound is preferably an alicyclic diisocyanate having 4 to 18 carbon atoms, examples of which include 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (HMDI). Examples of aromatic isocyanates include tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate.

[0190] It is preferable that the urethane resin contains an acid structure. This is because it is possible to disperse the resin in water even if a small amount of surfactant is added, and the water resistance of the functional layer is improved. This is called a self-emulsifying type, which means that the urethane resin can be dispersed and stabilized in water only by molecular ionicity without using a surfactant.

[0191] Examples of the acid structure include acid groups such as a carboxyl group (-COOH) and a sulfonic acid group (-SO3H). The acid structure may be present in a side chain or at a terminal in the urethane resin.

[0192] The acid value of the urethane resin is preferably 20 to 250 mgKOH / g, and more preferably 25 to 150 mgKOH / g. If the acid value is less than 20 mgKOH / g, the water dispersibility tends to be insufficient, and if the acid value is more than 250 mgKOH / g, the water resistance of the functional layer tends to be poor.

[0193] It is preferable that the acid structure is partially or entirely neutralized. By neutralizing the acid structure, the water dispersibility of the urethane resin can be improved. Examples of the neutralizing agent for neutralizing the acid structure include organic amines such as trimethylamine, triethylamine, tripropylamine, tributylamine, N-methyldiethanolamine, and triethanolamine; and inorganic bases such as sodium hydroxide and potassium hydroxide.

[0194] Examples of commercially available urethane resins include the "Superflex" series manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0195] <Other ingredients> The functional layer may further contain other components as necessary. The functional layer according to the present invention may contain a crosslinking agent. Examples of the crosslinking agent include epoxy-based, isocyanate-based, melamine-based, carbodiimide-based, and oxazoline-based crosslinking agents. Among these, carbodiimide-based and oxazoline-based crosslinking agents are preferred.

[0196] As the carbodiimide crosslinking agent, a compound having a plurality of carbodiimide structures in the molecule is preferred. By including such a compound, it is easy to effectively prevent the particles B included in the functional layer from peeling off. Compounds having a plurality of carbodiimide groups in the molecule can be used without any particular limitation. Polycarbodiimide is usually synthesized by a condensation reaction of an organic diisocyanate, but the organic group of the organic diisocyanate used in this synthesis is not particularly limited, and either an aromatic system or an aliphatic system, or a mixture of these systems can be used. From the viewpoint of reactivity, an aliphatic system is particularly preferred. As the synthesis raw material, an organic isocyanate, an organic diisocyanate, an organic triisocyanate, etc. are used. As an example of the organic isocyanate, those described in paragraph

[0024] of JP-A-2009-220316 can be used. In addition, the carbodiimide crosslinking agent used in the present invention may be a commercially available product, specifically, Carbodilite V-02-L2 manufactured by Nisshinbo Co., Ltd., etc. can be mentioned.

[0197] As the oxazoline-based crosslinking agent, those described in paragraph

[0078] of JP2012-231029A can be used. In addition, commercially available products may be used, such as EPOCROS K2010E, K2020E, K2030E, WS500, and WS700 manufactured by Nippon Shokubai Kagaku Kogyo Co., Ltd.

[0198] The crosslinking agent used in the present invention is preferably added in the range of 0.5 to 50 mass % relative to the total amount of solids in the functional layer, and more preferably added in the range of 1 to 30 mass %. By adding an amount of 1 mass % or more, peeling of particles contained in the functional layer can be effectively prevented. On the other hand, by adding an amount of 50 mass % or less, the surface condition tends to be further improved. Two or more types of crosslinking agents may be included, and when two or more types are included, the total amount is preferably within the above range.

[0199] The thickness of the functional layer is not particularly limited, but is preferably 0.01 to 1 μm. If the thickness of the functional layer is 0.01 μm or more, it is easy to effectively prevent the particles B contained in the functional layer from peeling off. If the thickness of the functional layer is 1 μm or less, it is possible to prevent the thickness of the polarizing plate from becoming excessively thick. The thickness of the functional layer is more preferably 0.02 to 0.5 μm.

[0200] [2.2] Particle B The particles B according to the present invention can be the same as the particles A. From the viewpoints of antiblocking property, suppression of particle dropout, and transparency, it is preferable that the number average particle diameter of the primary particles of the particles B is within a range of 50 to 500 nm, and that the ratio R (RB / RA) of the number average particle diameter (RB) of the primary particles of the particles B to the number average particle diameter (RA) of the primary particles of the particles A is within a range of 2.5 to 100.0.

[0201] The particles B are preferably silica particles, and can be dry powdered silica produced by burning silicon tetrachloride, or colloidal silica in which silicon dioxide or its hydrate is dispersed in water. When dry powdered silica is used, it can be added to the aqueous composition by dispersing it in water using an ultrasonic disperser or the like. Specific examples include, but are not limited to, the Sea Hoster series such as Sea Hoster KE-P10 and KE-P30 (manufactured by Nippon Shokubai Co., Ltd.) and the Snowtex series such as Snowtex OZL-35 (manufactured by Nissan Chemical Industries, Ltd.). The addition ratio of the silica particles B is preferably 1 to 15 parts by mass, more preferably 3 to 10 parts by mass, based on 100 parts by mass of the binder resin. These silica particles may be surface-treated with a hydrophobizing agent, similar to the particles A.

[0202] As the hydrophobic treatment agent, the above-mentioned general silane coupling agents, titanate coupling agents, aluminate coupling agents, various silicone oils, silicone oils, fatty acids, fatty acid metal salts, etc. can be used.

[0203] [2.3] Method for forming functional layer A method for forming the functional layer in the present invention will be described.

[0204] The method for forming the functional layer in the present invention is not particularly limited, and it is preferable to use a formation method such as a conventionally known wet coating method (also called a "wet process").

[0205] Wet coating methods include spin coating, casting, inkjet printing, printing, die coating, blade coating, roll coating, spray coating, curtain coating, and LB method (Langmuir-Blodgett method), among which methods highly suitable for roll-to-roll systems such as die coating, roll coating, inkjet printing, and spray coating are preferred from the standpoint of ease of obtaining a homogeneous thin film and high productivity.

[0206] Examples of liquid media that can be used to dissolve or disperse the binder resin used in the functional layer include water, alcohols such as methanol, ethanol, and isopropanol, ketones such as methyl ethyl ketone and cyclohexanone, fatty acid esters such as ethyl acetate, halogenated hydrocarbons such as dichlorobenzene, aromatic hydrocarbons such as toluene, xylene, mesitylene, and cyclohexylbenzene, aliphatic hydrocarbons such as cyclohexane, decalin, and dodecane, and organic solvents such as DMF and DMSO.

[0207] The particle B can be dispersed by a dispersion method such as ultrasonic dispersion, high shear force dispersion, or media dispersion.

[0208] FIG. 3 is a schematic diagram illustrating a preferred embodiment in which a functional layer is formed on a substrate film.

[0209] The convex portion height X shown below is preferably in the range of 40 to 400 nm. If it is 40 nm or more, an anti-blocking effect due to the unevenness formed in the functional layer is easily obtained. If it is 400 nm or less, film scratches and falling off of particles B contained in the functional layer are unlikely to occur. This is thought to be because particles B contained in the functional layer are easily covered by the binder resin of the functional layer.

[0210] Convex height = particle B diameter of functional layer - resin thickness of functional layer In Figure 3, X=ZY (X represents the height of the convex portion, Y represents the thickness of the resin, and Z represents the particle size of particle B.)

[0211] In addition, in the functional layer according to the present invention, in the formation of the coating film of the functional layer by the wet coating method, coating is performed two or more times, the first coating is a coating liquid containing the binder resin and the particle B on the base film, the second and subsequent coatings are further coated on the coating film formed by the first coating, and the second and subsequent coatings are the last coatings of the surface layer, which is formed by a coating liquid containing the binder resin but not the particle B, so that film scratches and the particle B contained in the functional layer are less likely to fall off, and is therefore preferable (see FIG. 2B). The thickness of the surface layer is appropriately determined when setting the height of the convex portion, and is preferably in the range of 5 to 100 nm, more preferably in the range of 10 to 50 nm.

[0212] [3] Manufacturing method of film roll As a method for producing the film roll of the present invention, a typical production method such as an inflation method, a T-die method, a calendar method, a cutting method, a casting method, an emulsion method, or a hot press method can be used for forming the base film. From the viewpoints of suppressing coloration, suppressing foreign matter defects, and suppressing optical defects such as die lines, the film formation method is preferably a solution casting method or a melt casting method, and in particular, the solution casting method is more preferable from the viewpoint of imparting high functionality by using various additives since the temperature in the processing step is low.

[0213] <Solution casting method> In the case of forming a film by the solution casting method, the method of manufacturing a film roll of the present invention preferably includes the steps of dissolving and dispersing a thermoplastic resin and additives such as the above-mentioned particle A in a solvent to prepare a dope (dissolving step; dope preparation step), casting the dope onto an endless metal support that moves indefinitely (casting step), drying the cast dope as a web (solvent evaporation step), peeling it off from the metal support (peeling step), drying, stretching, and width retention steps (stretching, width retention, drying step), and winding the finished film into a roll (winding step). As the thermoplastic resin, it is particularly preferable to use a cycloolefin resin or an acrylic resin.

[0214] FIG. 4 is a schematic diagram showing an example of a dope preparation step, a casting step, and a drying step (solvent evaporation step) of a solution casting film-forming method.

[0215] The large aggregates are removed from the feed kettle A41 by a filter A44, and the liquid is sent to the stock kettle A42. After that, various additive liquids are added from the stock kettle A42 to the main dope dissolving kettle A1.

[0216] Then, the main dope is filtered in the main filter A3, and the additive solution is added in-line from A16.

[0217] In many cases, the main dope contains about 10 to 50 mass % of the return material.

[0218] Recycled material is finely crushed film, and is made from film rolls that have had both sides cut off during the film production process, or rolls of film that have fallen out of spec due to scratches or other reasons.

[0219] As the raw material of the resin used for preparing the dope, a base resin, such as a cycloolefin resin, an acrylic resin, and other additives, which are previously pelletized, can be preferably used.

[0220] Each step will be described below.

[0221] 1) Dissolving process (dope preparation process) Hereinafter, as one embodiment of the present invention, a dissolving process will be described using a case where a cycloolefin resin (hereinafter, also referred to as "COP") is used as a thermoplastic resin as an example, but the present invention is not limited thereto.

[0222] This process is a process in which the COP and, if necessary, other compounds are dissolved in a solvent mainly consisting of a good solvent for the COP in a dissolution vessel while stirring to form a dope, or a process in which, if necessary, other compound solutions are mixed with the COP solution to form a dope, which is a main solution.

[0223] The concentration of COP in the dope is preferably high because it reduces the drying load after casting onto the metal support, but if the concentration of COP is too high, the load during filtration increases and the filtration accuracy deteriorates. The concentration that satisfies both of these requirements is preferably 10 to 35% by mass, more preferably 15 to 30% by mass.

[0224] The solvent used in the dope may be used alone or in combination of two or more kinds. However, it is preferable to use a mixture of a good solvent and a poor solvent for COP in terms of production efficiency, and it is preferable to use a large amount of the good solvent in terms of solubility of COP.

[0225] The preferred range of the mixing ratio of the good solvent to the poor solvent is 70 to 98 mass % of the good solvent and 2 to 30 mass % of the poor solvent. A good solvent is one that dissolves the COP used alone, and a poor solvent is one that swells or does not dissolve the COP alone. Therefore, the good solvent and poor solvent change depending on the average substitution degree of the COP.

[0226] The good solvent used in the present invention is not particularly limited, and examples thereof include organic halogen compounds such as methylene chloride, dioxolanes, acetone, methyl acetate, methyl acetoacetate, etc. Particularly preferred are methylene chloride and methyl acetate.

[0227] The poor solvent used in the present invention is not particularly limited, but preferably used are, for example, methanol, ethanol, n-butanol, cyclohexane, cyclohexanone, etc. The dope preferably contains 0.01 to 2% by mass of water.

[0228] In addition, the solvent used to dissolve COP is removed from the film by drying in the film production process and recovered, and then reused.

[0229] The recovered solvent may contain small amounts of additives added to the COP, such as plasticizers, ultraviolet absorbers, polymers, and monomer components. Even if these are contained, the recovered solvent can be preferably reused, and if necessary, it can be purified and reused.

[0230] The method of dissolving COP when preparing the above-mentioned dope can be a general method. Specifically, the method of dissolving COP under normal pressure, the method of dissolving COP under lower pressure than the boiling point of the main solvent, and the method of dissolving COP under higher pressure than the boiling point of the main solvent are preferable. By combining heating and pressurization, the COP can be heated to the boiling point under normal pressure or higher.

[0231] In addition, a method of stirring and dissolving while heating at a temperature equal to or higher than the boiling point of the solvent at normal pressure and within a range in which the solvent does not boil under pressure is also preferred in order to prevent the generation of lumpy undissolved matter called gel or solid matter.

[0232] Also preferably used is a method in which COP is mixed with a poor solvent to wet or swell it, and then a good solvent is added to dissolve it.

[0233] Pressurization may be performed by injecting an inert gas such as nitrogen gas or by increasing the vapor pressure of the solvent by heating. Heating is preferably performed from the outside, and for example, a jacket type is preferable because it is easy to control the temperature.

[0234] The heating temperature after adding the solvent is preferably high from the viewpoint of solubility of the COP. However, if the heating temperature is too high, the required pressure increases, resulting in poor productivity.

[0235] The heating temperature is preferably 45 to 120° C., more preferably 60 to 110° C., and even more preferably 70 to 105° C. The pressure is adjusted so that the solvent does not boil at the set temperature.

[0236] Alternatively, a cooling dissolution method is also preferably used, by which COP can be dissolved in a solvent such as methyl acetate.

[0237] Next, it is preferable to filter the COP solution (the dope during or after dissolution) using a suitable filter material such as filter paper.

[0238] As a filter material, it is preferable that the absolute filtration accuracy is small in order to remove insoluble matters, but if the absolute filtration accuracy is too small, there is a problem that the filter material is easily clogged. Therefore, a filter material with an absolute filtration accuracy of 0.008 mm or less is preferable, a filter material with an absolute filtration accuracy of 0.001 to 0.008 mm is more preferable, and a filter material with an absolute filtration accuracy of 0.003 to 0.006 mm is even more preferable.

[0239] There are no particular limitations on the material of the filter medium, and any ordinary filter medium can be used, but filter medium made of plastics such as polypropylene or Teflon (registered trademark), or filter medium made of metals such as stainless steel are preferred as they do not easily lose fibers.

[0240] It is preferable to remove or reduce impurities, particularly bright spot foreign matter, contained in the raw COP by filtration.

[0241] Bright spot foreign matter is a point (foreign matter) that is seen as light leaking from the opposite side when two polarizing plates are placed in a cross-Nicol state, a film or the like is placed between them, and light is applied from one polarizing plate side and observed from the other polarizing plate side. The number of bright spots is 200 / cm and is 0.01 mm or more in diameter. 2 It is preferable that the number of particles is 100 / cm or less. More preferable is 100 particles / cm. 2More preferably, 50 pieces / m 2 More preferably, 0 to 10 particles / cm 2 It is also preferable that there are fewer bright spots of 0.01 mm or less.

[0242] The dope can be filtered by a conventional method. However, a method of filtering the dope while heating the dope at a temperature equal to or higher than the boiling point of the solvent at normal pressure and within a range where the solvent does not boil under pressure is preferred because the increase in the difference in filtration pressure (called differential pressure) before and after filtration is small.

[0243] The temperature is preferably 45 to 120°C, more preferably 45 to 70°C, and even more preferably 45 to 55°C.

[0244] The filtration pressure is preferably small, and is preferably 1.6 MPa or less, more preferably 1.2 MPa or less, and even more preferably 1.0 MPa or less.

[0245] 2) Casting process Then, the dope is cast onto a metal support, that is, this step is a step in which the dope is sent to a pressurizing die A30 through a liquid sending pump (e.g., a pressurizing type constant volume gear pump) and cast from the pressurizing die slit onto a casting position on a metal support such as an endless metal belt A31, e.g., a stainless steel band, which moves indefinitely, or a rotating metal drum.

[0246] A pressure die is preferred because it is possible to adjust the slit shape of the die nozzle and to easily make the film thickness uniform. Pressure dies include coat hanger dies and T-dies, and any of them are preferably used. The surface of the metal support is preferably a mirror surface. In order to increase the film production speed, two or more pressure dies may be provided on the metal support, and the dope amount may be divided and layered. Alternatively, it is also preferred to obtain a film roll with a laminated structure by a co-casting method in which multiple dopes are cast simultaneously.

[0247] The casting width is preferably 1.3 m or more from the viewpoint of productivity. More preferably, it is 1.3 to 4.0 m. If it exceeds 4.0 m, there is a risk that stripes will appear during the manufacturing process and stability will decrease in the subsequent transport process. Even more preferably, it is 1.3 to 3.0 m from the viewpoints of transportability and productivity.

[0248] The metal support used in the casting step is preferably one with a mirror-finished surface, and the metal support is preferably a stainless steel belt or a cast drum with a plated surface.

[0249] The surface temperature of the metal support in the casting process is from -50°C to a temperature lower than the boiling point of the solvent. A higher temperature is preferable because it increases the drying speed of the web. However, if the temperature is too high, the web may foam or its flatness may deteriorate.

[0250] The support temperature is preferably 0 to 55° C., more preferably 22 to 50° C. Alternatively, it is also a preferred method to gel the web by cooling it and peel it off from the drum in a state where the web contains a large amount of residual solvent.

[0251] The method for controlling the temperature of the metal support is not particularly limited, but includes blowing hot or cold air or contacting the back side of the metal support with hot water. Using hot water is preferable because heat is transferred more efficiently and the time required for the temperature of the metal support to become constant is shorter. When using hot air, air at a temperature higher than the desired temperature may be used.

[0252] 3) Solvent evaporation process In this step, a web (a dope film formed by casting the dope on a casting support is called a web) is heated on the casting support to evaporate the solvent.

[0253] The solvent can be evaporated by blowing air from the web side and / or by transferring heat from the back side of the support using a liquid, or by transferring heat from the front and back sides using radiant heat, but the back side liquid heat transfer method is preferred because of its high drying efficiency. A combination of these methods is also preferably used. It is preferable to dry the web on the support after casting in an atmosphere of 35 to 100°C on the support. To maintain the atmosphere at 35 to 100°C, it is preferable to apply hot air at this temperature to the top surface of the web or heat it by means of infrared rays or the like.

[0254] From the viewpoints of surface quality, moisture permeability, and releasability, it is preferable to peel the web from the support within 30 to 120 seconds.

[0255] 4) Peeling process Next, the web is peeled off from the metal support. That is, in this process, the web from which the solvent has evaporated on the metal support is peeled off at the peeling position. The peeled web is sent to the next process.

[0256] The temperature at the peeling position on the metal support is preferably within the range of -50 to 40°C, more preferably within the range of 10 to 40°C, and most preferably within the range of 15 to 30°C.

[0257] The amount of residual solvent in the web on the metal support at the time of peeling is appropriately adjusted depending on the strength of the drying conditions, the length of the metal support, etc. In order for the film to have good flatness, the amount of residual solvent when the web is peeled off from the metal support is preferably 10 to 150% by mass. If the web is peeled off at a time when the amount of residual solvent is greater, if the web is too soft, the flatness at the time of peeling is impaired and wrinkles or vertical streaks are likely to occur due to the peeling tension, so the amount of residual solvent at the time of peeling is determined taking into account the economic speed and quality. More preferably, the amount is 20 to 40% by mass or 60 to 130% by mass, and particularly preferably, 20 to 30% by mass or 70 to 120% by mass.

[0258] In the present invention, the amount of residual solvent is defined by the following formula.

[0259] Residual solvent amount (mass%) = [(MN) / N] x 100 Here, M is the mass of a sample taken at any time during or after the production of the web or film, and N is the mass of M after heating at 115° C. for 1 hour.

[0260] The peel tension when peeling the film from the metal support is preferably 300 N / m or less. More preferably, it is in the range of 196 to 245 N / m, but if wrinkles are likely to occur during peeling, peeling is preferably performed with a tension of 190 N / m or less. Peeling is preferably performed with a peel tension of 300 N / m or less.

[0261] 5)Drying / stretching / width maintenance process (Dry) In the film drying process, the web is peeled off from the metal support and further dried to reduce the residual solvent content to preferably 1% by mass or less, more preferably 0.1% by mass or less, and particularly preferably 0 to 0.01% by mass or less.

[0262] In the film drying process, generally, a roll drying method (a method in which the web is dried by passing it alternately between multiple rollers arranged above and below) or a tenter method in which the web is dried while being transported is used. For example, after peeling, the web is dried using a drying device 35 in which the web is transported by passing it alternately between multiple rollers arranged in the drying device, and / or a tenter stretching device 34 in which both ends of the web are clipped with clips and transported.

[0263] There are no particular limitations on the means for drying the web, and hot air, infrared rays, heated rollers, microwaves, etc. can generally be used, but hot air is preferred for simplicity. Drying too quickly can easily damage the flatness of the finished film. Drying at high temperatures is preferably carried out when the residual solvent is about 8% by mass or less. Overall, drying is generally carried out within the range of about 30 to 250°C. Drying within the range of 35 to 200°C is particularly preferred. It is preferred to increase the drying temperature stepwise.

[0264] When using a tenter stretching machine, it is preferable to use a machine that can independently control the film gripping length (the distance from the gripping start to the gripping end) on the left and right sides by the left and right gripping means of the tenter. It is also preferable to intentionally create sections with different temperatures in the tenter process to improve flatness.

[0265] It is also preferable to provide a neutral zone between the different temperature zones so that each zone does not interfere with the other.

[0266] (Stretching / width retention) Subsequently, it is preferable to stretch the web peeled off from the metal support in at least one direction. The orientation of the molecules in the film can be controlled by the stretching process. In order to obtain the target retardation values ​​Ro and Rt in the present invention, it is preferable that the film has the structure of the present invention, and further, the refractive index is controlled by controlling the conveying tension and the stretching operation. For example, it is possible to vary the retardation value by lowering or increasing the tension in the longitudinal direction.

[0267] As a specific stretching method, biaxial stretching or uniaxial stretching can be performed sequentially or simultaneously in the longitudinal direction of the web (film-forming direction; casting direction; MD direction) and the direction perpendicular to the web surface, i.e., the width direction (TD direction). A biaxially stretched film is preferably biaxially stretched in the casting direction (MD direction) and the width direction (TD direction), but the film according to the present invention may be a uniaxially stretched film or an unstretched film. The stretching operation may be divided into multiple stages. When biaxial stretching is performed, simultaneous biaxial stretching may be performed, or it may be performed stepwise. In this case, stepwise means, for example, that stretching in different stretching directions can be performed sequentially, or stretching in the same direction can be divided into multiple stages and stretching in a different direction can be added to any of the stages.

[0268] For example, the following stretching step is also possible: Stretch in casting direction → Stretch in width direction → Stretch in casting direction → Stretch in casting direction Stretch in width direction → Stretch in width direction → Stretch in casting direction → Stretch in casting direction Simultaneous biaxial stretching also includes a case where the film is stretched in one direction and contracted by relaxing the tension in the other direction.

[0269] The final stretching ratio in the two mutually perpendicular axial directions is preferably 0.8 to 1.5 times in the casting direction and 1.1 to 2.5 times in the width direction, and more preferably 0.8 to 1.2 times in the casting direction and 1.2 to 2.0 times in the width direction.

[0270] The stretching temperature is usually preferably within the range of Tg of the resin constituting the film to Tg+60° C. In general, the stretching temperature is preferably 120 to 200° C., and more preferably 120 to 180° C.

[0271] The residual solvent in the web during stretching is preferably 20 to 0 mass %, more preferably 15 to 0 mass %.

[0272] There is no particular limitation on the method of stretching the web. For example, there is a method in which a plurality of rollers are provided with different peripheral speeds and the difference in roller peripheral speed is used to stretch the web in the longitudinal direction, a method in which both ends of the web are fixed with clips or pins and the distance between the clips or pins is increased in the traveling direction to stretch the web in the longitudinal direction, a method in which the web is similarly spread in the lateral direction and stretched in the lateral direction, or a method in which the web is spread in both the longitudinal and lateral directions at the same time to stretch the web in both the longitudinal and lateral directions. Of course, these methods may be used in combination. Among them, it is particularly preferable to stretch the web in the width direction (lateral direction) using a tenter method in which both ends of the web are held by clips or the like.

[0273] In the case of the so-called tenter method, it is preferable to drive the clip portion by a linear drive system, since this allows smooth stretching and reduces the risk of breakage.

[0274] In the film-forming process, the width holding or transverse stretching is preferably carried out by a tenter, and either a pin tenter or a clip tenter may be used.

[0275] The slow axis or fast axis of the film of the present invention exists in the film plane, and if the angle it makes with the film-forming direction is θ1, then θ1 is preferably −1° or more and +1° or less, and more preferably −0.5° or more and +0.5° or less.

[0276] This θ1 can be defined as an orientation angle, and θ1 can be measured using an automatic birefringence meter KOBRA-21ADH (manufactured by Oji Scientific Instruments Co., Ltd.) When θ1 satisfies the above relationships, it can contribute to obtaining high brightness in a displayed image and suppressing or preventing light leakage, and can contribute to obtaining faithful color reproduction in a color liquid crystal display device.

[0277] 6) Winding process Finally, the obtained web (finished film) is wound up to obtain a film roll. More specifically, after the residual solvent content in the web becomes 2% by mass or less, the web is wound up as a film by a winding machine A37. By reducing the residual solvent content to 0.4% by mass or less, a film with good dimensional stability can be obtained. In particular, it is preferable to wind up the web when the residual solvent content is in the range of 0.00 to 0.10% by mass.

[0278] The winding method may be any commonly used method, such as a constant torque method, a constant tension method, a taper tension method, or a program tension control method with constant internal stress, and any of these may be used appropriately.

[0279] Before being wound, the ends are slit and cut to the width to be the product, and the knurling and surface modification treatment used in the present invention are applied to both ends of the film to prevent sticking and scratches during winding.

[0280] The clips on both ends of the film are usually cut off because the film is deformed and cannot be used as a product. If the material has not deteriorated due to heat, it can be reused after collection.

[0281] The film roll of the present invention is preferably a long film, specifically, about 100 to 10,000 m, and is usually provided in a roll form.

[0282] <Details of film winding method> The winding method preferably includes a straight winding step of winding the film around a core so that the side edges of the film are aligned, and, after the straight winding step, an oscillating winding step of winding the film around the core by periodically vibrating the film or the core in the width direction of the film so that the side edges are periodically misaligned within a certain range in the width direction of the film.

[0283] In particular, it is preferable to switch from the straight winding process to the oscillating winding process when the wound length of the film reaches a switching winding length that is determined in advance within a range of 10 to 30% of the total wound length of the film.

[0284] It is preferable that the film winding device comprises a film winding unit that rotates the core to wind the film onto the core, an oscillating unit that vibrates the film or the core in the width direction of the film in conjunction with the winding of the film so that the film becomes an oscillating winding on the core that is periodically shifted within a certain range in the width direction of the film, and a switching unit that switches the winding of the film from the straight winding to the oscillating winding when the winding length of the film reaches a predetermined switching winding length.

[0285] The oscillatory winding will be described below.

[0286] As shown in FIG. 5, the film production line B10 includes a film production apparatus B11 and a winding apparatus B12. The film production apparatus B11 produces a film B13 by a solution casting method. In the solution casting method, a dope is prepared using a raw material. Then, the prepared dope is cast on an endless support to form a casting film. When the casting film has a self-supporting property, the casting film is peeled off from the endless support. The peeled casting film is dried with hot air or the like to form a film B13. The formed film B13 is sent to a winding apparatus B12 via a knurling roller B15. The knurling roller B15 forms minute irregularities on both side edges (edges) in the width direction of the film B13 by embossing or the like. The height of the irregularities formed by the knurling roller is preferably in the range of 0.5 to 20 μm.

[0287] 5 and 6, the winding device B12 includes a winding shaft B19, a core holder B20, a core B21, a turret B22, guide rollers B23 and B24, a dancer roller B25, an encoder B27, an oscillating unit B29, a winding motor B30, a controller B31, and a dancer unit B32. The size of the film to be wound by the winding device B12 is not particularly limited, but it is preferable that the total winding length is in the range of 2000 to 10000 m and the width is in the range of 500 to 2500 mm.

[0288] As shown in FIG. 5, the winding shaft B19 is attached to the turret B22 by a cantilever support mechanism. The cantilever support mechanism is a mechanism that supports only one end of the winding shaft B19. A core B21 is attached to the winding shaft B19. Both ends of the core B21 are clamped by a core holder B20 of the winding shaft B19. The core holder B20 is attached to the winding shaft B19 so as to be slidable in the axial direction (Y direction) of the winding shaft B19 and to be unrotatable. A winding motor B30 is connected to one end of the winding shaft B19 and configured to rotate the winding shaft B19. This rotation also rotates the core B21, allowing the film B13 to be wound around the core B21. This winding of the film B13 results in a film roll B38 in which the film B13 is wound in a roll shape.

[0289] A shift mechanism B28 is attached to the mounting end of the winding shaft B19 of the turret B22. This shift mechanism B28 reciprocates the winding core holder B20 in the axial direction on the winding shaft B19. This shift mechanism B28, the winding shaft B19, and the winding core holder B20 constitute an oscillating unit B29. By operating this oscillating unit B29 and causing the winding core holder B20 to reciprocate in the Y direction on the winding shaft B19 by the shift mechanism B28, the film B13 can be wound in an oscillating winding manner while the position of the side edge B13a shifts within the range of the amplitude Wo each time the film B13 is laminated. When the oscillating unit B29 is not operated, straight winding in which both side edges of the film B13 are aligned is possible. Switching between straight winding and oscillating winding is performed by a controller B31.

[0290] Here, in the oscillatory winding, the amplitude, or oscillation width Wo, can be set arbitrarily, and it is preferable that the amplitude Wo is within the range of 10 to 30 mm. Within the above range, the amplitude Wo may be fixed at a constant value, or may be gradually increased or decreased, or increased and then decreased.

[0291] The guide rollers B23, B24 and dancer roller B25 guide the film B13 from the film production device B11 in the transport direction (X direction). The dancer roller B25 adjusts the winding tension of the film B13 by moving the film B13 up and down (Z direction) using a shift mechanism B26. The shift mechanism B26 and dancer roller B25 form a dancer section B32. The encoder B27 transmits an encoder pulse signal to the controller B31 every time the guide roller B24 rotates by a certain rotation angle. The guide roller B24 may be provided with a tension sensor that measures the winding tension of the film B13.

[0292] The controller B31 controls the driving of the oscillation unit B29, the winding motor B30, and the dancer unit B32. The controller B31 includes a winding information input unit B39, an LUT memory B40, a switching time winding length specifying unit B41, a winding length measuring unit B42, and a switching determination unit B43. The winding information input unit B39 receives winding information such as the total winding length, thickness, width, outer diameter of the winding core B21, and winding tension of the film B13.

[0293] The LUT memory B40 stores the winding length of the film B13 when switching from straight winding to oscillating winding (winding length at switching) for each piece of winding information. The winding length at switching is preferably preset within a range of 10 to 30% of the total winding length of the film B13, and more preferably, is preset within a range of 15 to 25% of the total length of the film B13.

[0294] The timing for switching from straight winding to oscillating winding is preferably when the winding length is within the range of 15 to 25% of the total winding length.

[0295] In addition, when the winding length is switched from straight winding to oscillating winding when it is 10% or more of the total winding length, the surface pressure at the beginning of winding of the film B13 is more reliably prevented from dropping suddenly compared to when it is switched when it is less than 10%. This makes it possible to more reliably prevent the film roll B38 from loosening or becoming misaligned. In addition, when the winding length is switched after it exceeds 30% of the total winding length, the film B13 continues to be wound in straight winding even after it has left the negative region of the circumferential stress, so that the film roll B38 is more likely to develop edge elongation compared to when it is switched when it is 30% or less. Therefore, by switching from straight winding to oscillating winding when the winding length is 30% or less of the total winding length, edge elongation can be more reliably prevented compared to when it is switched after it exceeds 30%.

[0296] The winding length at switching determination unit B41 collates the winding information stored in the LUT memory B40 with the winding information input to the winding information input unit B39 to determine the winding length at switching corresponding to the input winding information. The winding length measurement unit B42 measures the winding length of the film B13 wound around the core B21 based on the encoder pulse signal from the encoder B27.

[0297] The switching determination unit B43 determines whether the winding length measured by the winding length measurement unit B42 exceeds the switching winding length specified by the switching winding length specification unit B41. If it is determined that the winding length exceeds the switching winding length, an oscillatory winding start signal is sent to the oscillation unit B29. Upon receiving the oscillatory winding start signal, the oscillation unit B29 changes the winding of the film B13 from straight winding, in which the film B13 is wound so that the side edges B13a of the film are aligned, to oscillatory winding, in which the film B13 is wound while shifting the position of the side edges B13a within the range of the amplitude Wo.

[0298] <Melt casting method> The film roll of the present invention can also be produced by a melt casting method.

[0299] The "melt casting method" refers to a method in which a composition containing a thermoplastic resin and additives such as the above-mentioned particle A is heated to a temperature at which it exhibits fluidity and melted, and then the melt containing the fluid thermoplastic resin is cast. Molding methods involving heating and melting can be specifically classified into melt extrusion molding, press molding, inflation molding, injection molding, blow molding, stretch molding, etc. Among these molding methods, the melt extrusion method is preferred from the viewpoints of mechanical strength and surface accuracy, etc. It is usually preferred that the raw materials used in the melt extrusion method are kneaded and pelletized in advance.

[0300] The pelletization may be carried out by a known method, for example, by feeding a dry cycloolefin resin, an acrylic resin, a plasticizer, or other additives to an extruder with a feeder, kneading the mixture using a single-screw or twin-screw extruder, extruding the mixture from a die in the form of strands, water-cooling or air-cooling, and cutting the mixture.

[0301] The additives may be mixed together before being fed to the extruder, or each may be fed in a separate feeder.

[0302] It is preferable to premix small amounts of additives such as particles and antioxidants in order to mix them uniformly.

[0303] It is preferable that the extruder is capable of pelletizing the resin so as to suppress shearing forces and prevent deterioration of the resin (reduction in molecular weight, coloring, gel formation, etc.), and that the processing temperature is as low as possible. For example, in the case of a twin-screw extruder, it is preferable to use deep-groove type screws that rotate in the same direction. For uniformity of kneading, an intermeshing type is preferable.

[0304] The pellets obtained as described above are used to form a film. Of course, it is also possible to feed the raw material powder directly to an extruder using a feeder without pelletizing, and form a film directly.

[0305] The melt temperature when the above pellets are extruded using a single-screw or twin-screw type extruder is in the range of 200 to 300°C. After filtering using a leaf disk type filter or the like to remove foreign matter, the pellets are cast into a film from a T-die, the film is nipped with a cooling roller and an elastic touch roller, and solidified on the cooling roller.

[0306] It is also preferable to use a method in which, when the material is introduced from the supply hopper into the extruder, it is placed under vacuum, reduced pressure, or an inert gas atmosphere to prevent oxidative decomposition, etc.

[0307] It is preferable to stabilize the extrusion flow rate by introducing a gear pump, etc. The filter used to remove foreign matter is preferably a stainless steel fiber sintered filter. A stainless steel fiber sintered filter is made by compressing stainless steel fibers that are intricately entangled, and sintering the contact points to integrate them. The density can be changed by changing the fiber thickness and the amount of compression, and the filtration accuracy can be adjusted.

[0308] Additives such as plasticizers and particles may be mixed with the resin in advance, or may be kneaded in during the extrusion process. In order to add them uniformly, it is preferable to use a mixing device such as a static mixer.

[0309] When the film is nipped with the cooling roller and the elastic touch roller, the temperature of the film on the touch roller side is preferably in the temperature range of the film's Tg to (Tg+110)° C. As the roller having an elastic surface used for this purpose, a known roller can be used.

[0310] The elastic touch roller is also called a pressing rotary body. As the elastic touch roller, a commercially available product can be used.

[0311] When the film is peeled off from the cooling roller, it is preferable to control the tension to prevent deformation of the film.

[0312] The film obtained as described above is preferably stretched by the stretching operation after passing through a step of contacting with cooling rollers.

[0313] The stretching method can be preferably performed using a known roller stretching machine, tenter, etc. Specific conditions are the same as those in the solution dripping method.

[0314] Finally, in the same manner as in the solution dripping method, the film obtained by forming the functional layer as described above is wound up to obtain the film roll of the present invention.

[0315] [4] Uses of film The film unwound from the film roll of the present invention is suitably used as an optical film, such as a protective film for a polarizing plate, and can be used in various optical measuring devices and display devices such as liquid crystal display devices and organic electroluminescence display devices. EXAMPLES

[0316] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, the terms "parts" and "%" are used, but they represent "parts by mass" or "% by mass" unless otherwise specified.

[0317] <Preparation of film roll 1: Film production by melt casting method> <Preparation of Base Film> A resin mixture was prepared according to the method described below, and a substrate film was produced using the resin composition shown in Table I by a melt casting film forming method.

[0318] (Pellet preparation) Acrylic resin: Polymethyl methacrylate (PMMA) 100% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.3% by mass The above-mentioned constituent materials were dried in a vacuum Nauta mixer at 70°C under reduced pressure for 3 hours, and then cooled to room temperature. The resulting mixture was melt-kneaded in a twin-screw extruder at 235°C and extruded into a strand shape. The resin composition extruded into a strand shape was water-cooled, and then cut to obtain pellets.

[0319] (Preparation of base film) The obtained pellets were put into a single screw extruder and melt-kneaded at 250°C under a nitrogen atmosphere. Then, the pellets were extruded from the die onto a first cooling roll having a surface temperature of 90°C. Then, the resin extruded onto the first cooling roll was pressed with a touch roll. The surface temperature of the touch roll was set to 80°C. Then, the obtained resin was further cooled and solidified on the second and third cooling rolls to obtain a film by a melt casting method.

[0320] The obtained film was stretched 1.5 times in the conveying direction (MD) at 125°C by zone stretching and 1.5 times in the width direction (TD) by tenter stretching at 125°C to adjust the film thickness to 40 μm. Then, it was slit to a film roll width of 2500 mm, and knurling processing of 10 mm width and 4 μm height was performed on both ends of the film to obtain a base film.

[0321] <Formation of functional layer> The following materials were used to form the functional layer.

[0322] Binder resin: Arrowbase SE1030N manufactured by Unitika Ltd.: Aqueous dispersion of modified polyolefin resin (modified polyethylene) Crosslinking agent: Epocross WS700 (manufactured by Nippon Shokubai Kagaku Kogyo Co., Ltd.): Aqueous dispersion of polyoxazoline compound Particle B: Sea Hoster KE-P30 manufactured by Nippon Shokubai Co., Ltd.: silica particle powder, number average particle size of primary particles: 300 nm Dispersion medium: water

[0323] (Preparation of particle B dispersion) SeaHostar KE-P30 was mixed with water and ultrasonically dispersed to prepare an aqueous dispersion. The dispersion concentration was adjusted to 5% by mass.

[0324] (Preparation of Functional Layer Composition) A composition for functional layer was prepared by mixing Arrowbase SE1030N, Epocross WS700, a dispersion of particle B, and pure water. The solid content of the composition was 2.5% by mass, and the proportions of each component in the solid content were 91% by mass of binder resin, 5.0% by mass of crosslinking agent, and 4.0% by mass of particle B.

[0325] (Preparation of laminated film) The portion of one side of the substrate film that was not subjected to the knurling process was subjected to a corona discharge treatment. The electron irradiation dose in the corona discharge was 500 W / m 2 The prepared functional layer composition was applied to the corona-treated portion of the obtained base film using a bar coater so that the thickness of the binder resin after drying (Y in FIG. 3) was 100 nm, and then dried at 100° C. for 3 minutes to form a functional layer. As a result, a laminated film including the base film and the functional layer was obtained.

[0326] After the functional layer was formed, the laminated film was wound around a core, and the film roll 1 of the present invention was wound up to a roll length of 4000 m.

[0327] <Preparation of film roll 2> Film roll 2 was produced in the same manner as film roll 1, except that the base film did not contain particles A.

[0328] <Preparation of film roll 3: Film formation by solution casting method>

[0329] <Preparation of Base Film> Substrate films were prepared using the resin compositions shown in Table I by a solution casting method according to the following method. (Preparation of Microparticle Dispersion) Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 4% by mass Dichloromethane 48% by mass Ethanol 48% by mass The above was mixed and stirred for 50 minutes in a dissolver, then dispersed using a Manton-Gaulin.Furthermore, dispersion was performed using an attritor so that the secondary particle diameter became the specified size.Then, the mixture was filtered using Finemet NF manufactured by Nippon Seisen Co., Ltd. to prepare a fine particle dispersion.

[0330] (Preparation of base film) First, dichloromethane was added to the pressurized dissolution tank at a flow rate of 400 kg / min and ethanol at a flow rate of 20 kg / min. Three minutes after the start of the solvent addition, acrylic resin (PMMA) was added to the pressurized dissolution tank while stirring. Next, five minutes after the start of the solvent addition, the microparticle-added liquid was added so that the solid content of particle A was in the following condition, and this was heated to 60°C and completely dissolved while stirring. The heating temperature was increased from room temperature at a rate of 5°C / min, and after dissolving for 30 minutes, the temperature was decreased at a rate of 3°C / min. This was filtered using Azumi Filter Paper No. 244 (filtration accuracy 0.005 mm) manufactured by Azumi Filter Paper Co., Ltd. at a filtration flow rate of 300 L / m. 2 ·h, filtration pressure 1.0×10 6 The mixture was filtered at 1000 Pa to prepare a dope. (Preparation of dope) Acrylic resin (PMMA) 100% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.30% by mass Dichloromethane 360% by mass Ethanol 40% by mass Next, using an endless belt casting device, the dope was uniformly cast on a stainless steel belt support at a temperature of 31°C and a width of 2300 mm. The temperature of the stainless steel belt was controlled at 28°C. The conveying speed of the stainless steel belt was 30 m / min. The solvent was evaporated until the residual solvent amount in the cast film was 25% by mass on the stainless steel belt support, and then the film was peeled off from the stainless steel belt support at a peeling tension of 100 N / m. The film was stretched while being heated in the conveying direction (MD direction) by a roll method using the peripheral speed difference of the conveying roll, and then stretched while being heated in the TD direction by a tenter method, and then conveyed while being heated at 60°C until it was completely dried, so that the final film thickness was 40 μm. The film was further slit to a width of 2500 mm, and then knurled at both ends of the film to a width of 10 mm and a height of 4 μm.

[0331] The web was stretched in the MD direction at a residual solvent content of 15% by mass, heated at 90°C, and stretched at a ratio of 5%. The web was stretched in the TD direction at a residual solvent content of 5% by mass, stretched at a ratio of 20% by mass, and heated at 105°C.

[0332] <Formation of functional layer> The preparation of particle B dispersion, the preparation of the composition for the functional layer, and the production of the laminated film were carried out in the same manner as in the production of film roll 1. After the functional layer was formed, the laminated film was wound around a core, and film roll 3 of the present invention was wound to a winding length of 4,000 m.

[0333] <Preparation of film roll 4> Film roll 4 was produced in the same manner as film roll 3, except that the particles A were not contained in the base film.

[0334] <Preparation of film roll 5> Film roll 5 was produced in the same manner as film roll 3, except that the dope was prepared and stretched under the following conditions. (Preparation of dope) Acrylic resin (PMMA) 100% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.30% by mass Polyester 1 (compound with the following structural formula) 10% by mass Dichloromethane 360% by mass Ethanol 40% by mass (Stretching conditions) The stretching in the MD direction was performed at a heating temperature of 90° C. and a stretching ratio of 40%, and the stretching in the TD direction was performed at a heating temperature of 95° C. and a stretching ratio of 60%.

[0335] (Polyester 1) The following polyester 1 was synthesized by a conventional method and used.

[0336] [ka]

[0337] <Preparation of film roll 6> Film roll 6 was produced in the same manner as film roll 5, except that the particles A were not contained in the base film.

[0338] <Preparation of film roll 7> Film roll 7 was produced in the same manner as film roll 3, except that the dope composition and stretching conditions were as follows. (Preparation of dope) Acrylic resin (PMMA) 100% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.30% by mass Polyester 1 (used for film roll 5) 15% by mass Dichloromethane 360% by mass Ethanol 40% by mass (Stretching conditions) Stretching in the MD direction was performed at a heating temperature of 85° C. and a stretching ratio of 40%, and stretching in the TD direction was performed at a heating temperature of 90° C. and a stretching ratio of 60%.

[0339] <Preparation of film roll 8> Film roll 8 was produced in the same manner as film roll 7, except that the base film did not contain particles A.

[0340] <Preparation of film roll 9> Film roll 9 was produced in the same manner as film roll 3, except that particles A contained in the base film were silica particles having a number-average particle size of primary particles of 3.5 nm.

[0341] <Preparation of film roll 10> Film roll 10 was produced in the same manner as film roll 3, except that particles A contained in the base film were silica particles having a number-average particle size of primary particles of 30 nm.

[0342] <Preparation of film roll 11> Film roll 11 was produced in the same manner as film roll 3, except that the amount of particles A contained in the base film was 0.03% by mass.

[0343] <Preparation of film roll 12> Film roll 12 was produced in the same manner as film roll 3, except that the amount of particles A contained in the base film was 3.0% by mass.

[0344] <Preparation of film roll 13> Film roll 13 was produced in the same manner as film roll 3, except that the particles A contained in the base film were acrylic particles. The acrylic particles were prepared as follows.

[0345] (Preparation of acrylic particles) (Production of seed particles) In a polymerization vessel equipped with a stirrer and a thermometer, 1000g of deionized water was placed, followed by 200g of methyl methacrylate (MMA) and 6g of t-dodecyl mercaptan, and the mixture was heated to 70°C while stirring and replacing with nitrogen. The internal temperature was kept at 70°C, and 20g of deionized water in which 1g of potassium persulfate had been dissolved as a polymerization initiator was added, followed by polymerization for 10 hours. The average particle size of the polymer particles in the resulting emulsion was 0.44μm. (Production of polymer particles) In a polymerization vessel equipped with a stirrer and a thermometer, 800 g of deionized water in which 3 g of polyoxyethylene tridecyl ether ammonium sulfate was dissolved was placed, and a mixture of 144 g of methyl acrylate, 22 g of styrene, and 34 g of ethylene glycol dimethacrylate as a monomer mixture, and 1 g of azobisisobutyronitrile as a polymerization initiator was placed therein. The mixture was then stirred with a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain a dispersion. Further, 60 g of the above emulsion containing seed particles was added to the dispersion liquid, and the mixture was stirred at 30°C for 1 hour to allow the seed particles to absorb the monomer mixture. The absorbed monomer mixture was then polymerized by heating at 50°C for 5 hours under a nitrogen stream, and then cooled to room temperature (about 25°C) to obtain a slurry containing polymer particles. The average particle size of the obtained polymer particles was 100 nm.

[0346] <Production of film roll 14: Film formation by melt casting method> (Pellet preparation) Cyclic polyolefin resin: R5000 (manufactured by JSR Corporation) 100% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.3% by mass The above-mentioned constituent materials were dried in a vacuum Nauta mixer at 70°C under reduced pressure for 3 hours, and then cooled to room temperature. The resulting mixture was melt-kneaded in a twin-screw extruder at 245°C and extruded into a strand shape. The resin composition extruded into a strand shape was water-cooled, and then cut to obtain pellets. <Preparation of Base Film> The obtained pellets were put into a single screw extruder and melt-kneaded at 260°C under a nitrogen atmosphere. Then, the pellets were extruded from the die onto a first cooling roll having a surface temperature of 90°C. Then, the resin extruded onto the first cooling roll was pressed with a touch roll. The surface temperature of the touch roll was set to 80°C. Then, the obtained resin was further cooled and solidified on the second and third cooling rolls to obtain a base film by a melt casting method. The obtained base film was stretched by 10% in the conveying direction (MD direction) at 145° C. by zone stretching and by 40% in the width direction (TD direction) at 145° C. by tenter stretching to adjust the film thickness to 40 μm. Then, it was slit to a film roll width of 2500 mm, and knurling processing of 10 mm width and 4 μm height was performed on both ends of the film to obtain a base film.

[0347] <Formation of functional layer> The preparation of particle B dispersion, the preparation of the composition for the functional layer, and the production of the laminated film were carried out in the same manner as in the production of film roll 1. After the functional layer was formed, the laminated film was wound around a core, and the film roll 14 of the present invention was wound to a winding length of 4,000 m.

[0348] <Preparation of film roll 15> Film roll 15 was produced in the same manner as film roll 14, except that the base film did not contain particles A.

[0349] <Preparation of film roll 16: Film formation by solution casting method> <Preparation of Base Film> (Preparation of Microparticle Dispersion) Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 4% by mass Dichloromethane 48% by mass Ethanol 48% by mass The above was mixed and stirred for 50 minutes in a dissolver, then dispersed using a Manton-Gaulin.Furthermore, dispersion was performed using an attritor so that the secondary particle diameter became the specified size.Then, the mixture was filtered using Finemet NF manufactured by Nippon Seisen Co., Ltd. to prepare a fine particle dispersion.

[0350] (Preparation of base film) First, dichloromethane was added to the pressurized dissolution tank at a flow rate of 400 kg / min and ethanol at a flow rate of 20 kg / min. Three minutes after the start of the solvent addition, cyclic polyolefin resin was added to the pressurized dissolution tank while stirring. Next, five minutes after the start of the solvent addition, the microparticle-added liquid was added so that the solid content of particle A was in the following condition, and this was heated to 60°C and completely dissolved while stirring. The heating temperature was increased from room temperature at a rate of 5°C / min, and after dissolving for 30 minutes, the temperature was decreased at a rate of 3°C / min. This was filtered using Azumi Filter Paper No. 244 (filtration accuracy 0.005 mm) manufactured by Azumi Filter Paper Co., Ltd. at a filtration flow rate of 300 L / m. 2 ·h, filtration pressure 1.0×10 6 The mixture was filtered at 1000 Pa to prepare a dope. (Preparation of dope) Cyclic polyolefin resin G7810 (JSR Corporation) 100% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.30% by mass Dichloromethane 380% by mass Ethanol 20% by weight Next, using an endless belt casting device, the dope was uniformly cast on a stainless steel belt support at a temperature of 31°C and a width of 2300 mm. The temperature of the stainless steel belt was controlled at 28°C. The conveying speed of the stainless steel belt was 30 m / min. The solvent was evaporated on the stainless steel belt support until the residual solvent amount in the cast film reached 30% by mass, and then the film was peeled off from the stainless steel belt support at a peeling tension of 110 N / m. The film was stretched while being heated in the conveying direction (MD direction) by a roll method using the peripheral speed difference of the conveying roll, and then stretched while being heated in the TD direction by a tenter method, and then conveyed while being heated at 70°C until it was completely dried, so that the final film thickness was 40 μm. The film was further slit to a width of 2500 mm, and then knurled at both ends of the film to a width of 10 mm and a height of 4 μm.

[0351] The web was stretched in the MD direction with a residual solvent content of 15% by mass, a heating temperature of 110°C, and a stretch ratio of 10%. The web was stretched in the TD direction with a residual solvent content of 5% by mass, a stretch ratio of 40%, and a heating degree of 140°C.

[0352] <Formation of functional layer> The preparation of particle B dispersion, the preparation of the composition for the functional layer, and the production of the laminated film were carried out in the same manner as in the production of film roll 1. After the functional layer was formed, the laminated film was wound around a core, and the film roll 16 of the present invention was wound to a winding length of 4,000 m.

[0353] <Preparation of film roll 17> Film roll 17 was produced in the same manner as film roll 16, except that the base film did not contain particles A.

[0354] <Preparation of film roll 18> A film roll 18 was produced in the same manner as the film roll 16, except that the dope was prepared and stretched under the following conditions. (Preparation of dope) Cyclic polyolefin resin G7810 (JSR Corporation) 100% by mass Polyester 1 (used for film roll 5) 10% by mass Particle A: R972V (manufactured by Nippon Aerosil Co., Ltd., silica particles, number average particle size of primary particles: 16 nm) 0.30% by mass Dichloromethane 380% by mass Ethanol 20% by weight (Stretching conditions) Stretching in the MD direction was performed at a heating temperature of 115° C. and a stretching ratio of 10%, and stretching in the TD direction was performed at a heating temperature of 130° C. and a stretching ratio of 40%.

[0355] <Preparation of film roll 19> Film roll 19 was produced in the same manner as film roll 18, except that the base film did not contain particles A.

[0356] <Preparation of film roll 20> Film roll 20 was produced in the same manner as film roll 18, except that the amount of polyester 1 used in the base film was 15 mass%, the MD stretching was performed at a heating temperature of 110°C and a stretching ratio of 10%, and the TD stretching was performed at a heating temperature of 125°C and a stretching ratio of 40%.

[0357] <Preparation of film roll 21> Film roll 21 was produced in the same manner as film roll 20, except that the particles A were not contained in the base film.

[0358] <Preparation of film roll 22> Film roll 22 was produced in the same manner as film roll 16, except that particles A contained in the base film were silica particles having a number-average particle size of primary particles of 3.5 nm.

[0359] <Preparation of film roll 23> Film roll 23 was produced in the same manner as film roll 16, except that particles A contained in the base film were silica particles having a number-average particle size of primary particles of 30 nm.

[0360] <Preparation of film roll 24> Film roll 24 was produced in the same manner as film roll 16, except that the amount of particles A contained in the base film was set to 0.03% by mass.

[0361] <Preparation of film roll 25> Film roll 25 was produced in the same manner as film roll 16, except that the amount of particles A contained in the base film was 3.0% by mass.

[0362] <Preparation of film roll 26> Film roll 26 was produced in the same manner as film roll 16, except that acrylic particles were used as particles A contained in the base film. The acrylic particles were the same as those used in film roll 13, except that the number-average particle size was adjusted to 50 nm.

[0363] <Preparation of film roll 27> Film roll 27 was produced in the same manner as film roll 16, except that in preparing the composition for the functional layer, polyester urethane (manufactured by Daiichi Kogyo Seiyaku, product name: Superflex 210, solid content: 33%) was used instead of Arrowbase SE1030N.

[0364] <Preparation of film roll 28> A film roll 28 was produced in the same manner as the film roll 16, except that in forming the functional layer, the thickness of the binder resin after drying was 280 nm.

[0365] <Preparation of film roll 29> Film roll 29 was produced in the same manner as film roll 16, except that the particle size of particles B used in the functional layer was 700 nm.

[0366] <Preparation of film roll 30> Film roll 30 was produced in the same manner as film roll 16, except that the particle size of particles B used in the functional layer was 50 nm, and the thickness of the binder resin after drying was 10 nm when the functional layer was formed.

[0367] <Preparation of film roll 31> Film roll 31 was produced in the same manner as film roll 16, except that the particle diameter of particles B used in the functional layer was 600 nm.

[0368] <Preparation of film roll 32> The particles B used in the functional layer were acrylic particles. Film roll 32 was produced in the same manner as film roll 16, except that the composition for the functional layer was prepared as follows.

[0369] (Preparation of Functional Layer Composition) A composition for the functional layer was prepared by combining Arrowbase SE1030N, Epocross WS700, acrylic particles ((Nippon Shokubai, Eposter MX-200W, solids content: 10%, primary particle size: 330 nm) and pure water. The solids concentration in the composition was 2.5%, and the proportions of each component in the solids were 91% by mass for the binder resin, 5.0% by mass for the crosslinking agent, and 4.0% by mass for the particles B.

[0370] <Preparation of film roll 33> The particles A contained in the base film were the same as the acrylic particles used in the film roll 13. The particles B used in the functional layer were the acrylic particles used in the film roll 32 in the same manner. Except for these, the film roll 33 was produced in the same manner as the film roll 16.

[0371] <Preparation of film roll 34> Film roll 34 was produced in the same manner as film roll 3, except that the functional layer was formed in the following manner.

[0372] (Preparation of Functional Layer Composition 1) A composition for functional layer was prepared by combining Arrowbase SE1030N, Epocross WS700, and particle B dispersion (silica particles; Seahoster KE-P30, primary particle diameter 300 nm). The solid content of the composition was 2.5%, and the proportions of each component in the solid content were 91% by mass of binder resin, 5.0% by mass of crosslinker, and 4.0% by mass of particle B.

[0373] (Preparation of Functional Layer Composition 2) A composition for functional layer was prepared by combining Arrowbase SE1030N and Epocross WS700. The solid content of the composition was 2.5%, and the proportion of each component in the solid content was 95% by mass for the binder resin and 5.0% by mass for the crosslinking agent.

[0374] (Preparation of laminated film) A corona discharge treatment was performed on one side of the substrate film that had not been subjected to knurling. The electron dose in the corona discharge was 500 W / m 2 / min. The prepared functional layer composition 1 was applied to the corona-treated portion of the obtained base film using a bar coater so that the dried thickness (Y in FIG. 3) was 100 nm, and then dried at 100°C for 3 minutes. The functional layer composition 2 was applied to the layer formed by the functional layer composition 1 using a bar coater so that the dried thickness was 30 nm, and then dried at 100°C for 1 minute. Thereby, a film roll 34 was obtained that included a base film and two functional layers, in which the convex particles were also covered with the functional layer, as shown in FIG. 2B.

[0375] <Preparation of film roll 35> The cyclic polyolefin resin film used in the production of the film roll 16 was prepared as the base film. A film roll 35 was obtained in the same manner as the film roll 34, except that this base film was used.

[0376] The film rolls 1 to 35 thus produced were used to carry out the following evaluations. In addition, in Tables I, II and III, "the present invention" in the remarks column for each of Film Roll Nos. 9, 10, 13, 22, 23, 26, 29, 30, 31 and 33 should be read as "Reference Example."

[0377] Evaluation (1) Measurement of elastic modulus of base film <Test method for tensile modulus> The film is cut into a size of 100 mm (MD) x 10 mm (TD) to obtain a test piece. This test piece is pulled in the MD (direction X) of the test piece in accordance with JIS K7127:1999 using an Orientec Tensilon RTC-1225A with a chuck distance of 50 mm, and the tensile modulus in the MD (direction X) is measured. The measurement was performed at 25°C and 55% RH. The unit is GPa.

[0378] (2) Surface roughness (Ra) The surface roughness (arithmetic mean roughness) Ra was calculated for the surface of the substrate film using an atomic force microscope (AFM) in accordance with the surface roughness standard (JIS B 0601-2001).

[0379] (3) Height of protrusion The height X of the protrusions of the functional layer shown in FIG. 3 was determined by randomly selecting 20 protrusions in an area of ​​5 cm × 5 cm on the film roll, and examining their cross sections using an optical microscope, using the following formula: Convex height = particle B diameter of functional layer - resin thickness of functional layer In Figure 3, X=ZY (X represents the height of the convex portion, Y represents the thickness of the resin, and Z represents the particle size of particle B.)

[0380] (4) Blocking The wound film roll was stored at 40°C and 80% RH for one week, after which the film was unwound from the roll and visually inspected for blocking (sticking) between overlapping pieces of film. Evaluation was based on the following criteria. ◎: No blocking ○: The amount of blocking is extremely small and does not pose a problem in practical use. △: There is a slight amount of blocking, but it is not a problem for practical use. ×: Significant blocking

[0381] (5) Film scratches The wound film roll was unwound and visually evaluated for the presence or absence of scratches (scratch resistance) using the following method. The side of the film roll opposite to the side on which the functional layer was formed was irradiated with light using a sodium lamp (KNL-35D, manufactured by Lightest Co., Ltd.) and a commercially available three-wavelength fluorescent lamp, and the occurrence of scratches was evaluated in a dark room. The area evaluated was the surface inside the edge, excluding a 5 cm area. ◎: No scratches ○: The amount of scratches is very small and there is no problem in practical use. △: There are a few scratches, but they do not affect the practical use. ×: Many scratches

[0382] (6) Falling off of particles contained in the functional layer The evaluation was carried out using a surface property tester (Tribostation TYPE32) manufactured by Shinto Scientific Co., Ltd. First, a nonwoven fabric (Bencotto, manufactured by Asahi Kasei Co., Ltd.) was placed on the frictional surface of the surface property tester, and the evaluation film was placed underneath it so that the functional layer surface of the film roll faced it, and a load of 200 g was applied and the film was run back and forth 10 times. After that, the adhesion state of the fallen fine particles on the surface of the nonwoven fabric was observed with an optical microscope (450x), and the particle shedding property of the film was evaluated according to the following criteria. ◎: No fallen particles were observed ○: The amount of particles that fell off was extremely small, and there was no problem in practical use. △: A small amount of particles have fallen off, but this does not pose a problem in practical use. ×: A large amount of fallen particles was observed The configurations of the film rolls and the evaluation results are shown in Tables I, II and III.

[0383] [Table 1]

[0384] [Table 2]

[0385] [Table 3]

[0386] It can be seen from Tables I, II and III that the film rolls of the present invention are superior to the comparative examples in blocking resistance, scratch resistance of the film and shedding of particles from the functional layer. Furthermore, as shown in FIG. 2B, film rolls 34 and 35 in which the convex particles were also covered with a functional layer were particularly excellent in blocking resistance, film scratch resistance, and particle shedding from the functional layer. [Industrial Applicability]

[0387] The film roll of the present invention has excellent antiblocking properties and suppresses the occurrence of scratches and particle drop-off due to contact between particles and the film surface, and is suitable for use as an optical film in various optical measuring devices, polarizing plates, and display devices such as liquid crystal display devices and organic electroluminescence display devices. [Explanation of symbols]

[0388] 1. Base film 2. Tiny gaps 3 Particle A 4 Particle B 5. Binder resin 6 Functional Layers 7. Binder Resin 10 Film Rolls A1 Melting pot A2, A5, A11, A14 Liquid delivery pump A3, A6, A12, A15 filter A4, A13 Stock Tank A8, A16 conduit A10 Additive preparation kettle A20 confluence pipe A21 Mixer A30 Die A31 Metal support A32 Web A33 Peeling position A34 Tenter device A35 Roller Dryer A36 Roller A37 Winder A41 Stock Tank A43 Pump A44 Filter B10 Film Production Line B11 Film manufacturing equipment B12 Winding device B13 Film B15 Knurling section B19 Winding shaft B20 core holder B21 Roll core B22 Turret B23, B24 guide rollers B25 Dancer Roller B26 Shift mechanism B27 Encoder B28 Shift mechanism B29 Oscillator section B30 Winding motor B31 Controller B32 Dance Club B39 Winding information input section B40 LUT memory section B41 Winding length specification part at switching B42 Winding length measurement unit B43 Switching judgment section

Claims

1. A film roll having a functional layer provided on one side of a base film, The elastic modulus of the base film at 25° C. and 55% RH is within the range of 1.0 to 3.0 GPa, The base film contains particles A, and The functional layer contains a binder resin and particles B, The number average particle diameter of the primary particles of the particle A is within a range of 5 to 20 nm, the number average particle diameter of the primary particles of the particle B is within a range of 50 to 500 nm, and the ratio R (RB / RA) of the number average particle diameter (RB) of the primary particles of the particle B to the number average particle diameter (RA) of the primary particles of the particle A is within a range of 2.5 to 100. A film roll comprising:

2. 2. The film roll according to claim 1, wherein the base film is a long film formed by casting a solution containing a resin and the particles A.

3. 3. The film roll according to claim 1, wherein the base film contains an acrylic resin or a cyclic olefin resin.

4. 4. The film roll according to claim 1, wherein the binder resin contained in the functional layer is a polyolefin resin.

5. 5. The film roll according to claim 1, wherein the particles A and the particles B are silica particles.

6. 6. The film roll according to claim 1, wherein the functional layer is composed of a plurality of layers, and a surface layer does not contain the particles B.

7. A method for producing the film roll according to any one of claims 1 to 6, comprising the steps of: A method for producing a film roll, comprising forming the base film by a solution casting method, and forming the functional layer by a wet coating method.

8. In forming a coating film of the functional layer by the wet coating method, coating is performed two or more times, In the first coating, a coating liquid containing the binder resin and the particles B is applied onto the base film to form a coating film, The second and subsequent coatings are performed by forming a coating film on the coating film formed by the first coating, The second or subsequent coating, which is the last coating of the surface layer, forms a coating film using a coating liquid that contains the binder resin but does not contain the particles B. The method for producing a film roll according to claim 7 .

Citation Information

Patent Citations

  • Inner cistern low temperature tank

    JP1980094096A

  • Method for producing cyclic olefin-based resin film, cyclic olefin-based resin film, polarizing plate, and liquid crystal display

    JP2007098643A

  • Adhesive type brassiere and method for producing the same

    JP2008007893A